When Scientific Reassessment Fails Citizen Science. Comment on Soldo, A. When Citizen Science Becomes Speculation: Evaluating the Reliability of Lamnid Shark Identification from Photographic Records in the Mediterranean. J. Mar. Sci. Eng. 2026, 14, 173 - Patrick L. Jambura; Julia Türtscher; Joshua K. Moyer; Kenshu Shimada; Ilija Ćetković; Branko Dragičević; Pero Ugarković; Mišo Pavičić; Phillip C. Sternes; Simone Niedermüller; Jacopo Bernardi; Matteo Barbato; et al. (Journal of Marine Science and Engineering, 2026)
Soldo [...]

Formation of three great Asian plateaus, climate change, and biodiversity - Guan-Long Cao; Xiao-Qian Li; Kun-Li Xiang; Andrey S. Erst; Florian Jabbour; Rosa Del C. Ortiz; Jian Yang; Wei Wang (Trends in Ecology & Evolution, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Rationale and Study Protocol for the Academy of Nutrition and Dietetics’ Breastfeeding Registry Study - Allison C. Gaubert; Julie M. Long; Lindsay Woodcock; Casey R. Colin; Lauri Wright; Hanadi Hamadi; Constantina Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2026)

Integrating borehole image log, core data, and computed tomography for characterizing natural open fractures in the Pre-salt Barra Velha Formation, Santos Basin, Brazil - Luiza de Carvalho Mendes; Gabriela F. Matheus; Ole P. Wennberg; Haili Long-Sanouiller; Mateus Basso; Juan F. Villacreses Morales; Guilherme F. Chinelatto; Alexandre C. Vidal (Journal of Structural Geology, 2026)

Ecology of community reassembly: Movements and diets of megafauna during a decade of restoration in Mozambique - Matthew C. Hutchinson; Reena H. Walker; Joel O. Abraham; Justine A. Becker; Dominique D. Gonçalves; Ciara M. Nutter; Johan Pansu; Erin M. Phillips; Arjun B. Potter; Beto Soares Tenente; Marc E. Stalmans; Ryan A. Long; et al. (Ecology, 2026)
The last decade has brought a worldwide surge of interest in rewilding—the repopulation of large herbivores and carnivores—as a strategy for conserving species and reviving ecosystem functions. Rewilding initiatives, if closely monitored, can provide unique insights into the ecology of the world's largest animals at otherwise impossible spatial and temporal scales. Capitalizing on these opportunities, and developing a knowledge base to guide future restoration efforts, requires the collection and dissemination of long‐term data that document community reassembly. To date, such data are virtually nonexistent: most megafaunal restoration projects are nascent and/or have not been rigorously monitored. Since 2008, the Gorongosa Restoration Project, in Mozambique's Gorongosa National Park, has facilitated the recovery of megafauna populations that were severely depleted or extirpated during the country's civil war (1977–1992). For over a decade, we have monitored Gorongosa's large‐herbivore populations to understand how animal behavior and trophic interactions change as communities reassemble. Here, we present spatiotemporally explicit data sets on the movements and diets of large herbivores in Gorongosa between 2013 and 2025, along with annual rainfall data. This period encompassed extremes of climate (including some of the driest and wettest years on record) and the reintroduction, starting in 2018, of locally extinct apex predators and scavengers: African wild dog ( Lycaon pictus ), leopard ( Panthera pardus ), spotted hyena ( Crocuta crocuta ), and side‐striped jackal ( Lupulella adusta ). We used GPS telemetry to monitor 277 herbivores of seven species (listed below with number of individuals collared, median duration of tracking, and median number of locations per individual): Cape bushbuck ( Tragelaphus sylvaticus : 103 individuals; 280 days; 6646 fixes), nyala ( T. angasii : 37 individuals; 306 days; 6789 fixes), greater kudu ( T. strepsiceros : 80 individuals; 300 days; 17,365 fixes), common eland ( T. oryx : 10 individuals; 334 days; 15,783 fixes), waterbuck ( Kobus ellipsiprymnus : 22 individuals; 13 days; 2877 fixes), plains zebra ( Equus quagga : 7 individuals; 212 days; 1171 fixes), and African savanna elephant ( Loxodonta africana : 18 individuals; 706 days; 33,122 fixes). For 295 individuals that were immobilized during this work, we present morphological measurements (chest girth, body length, hind‐foot length, weight), reproductive status and nutritional condition (ultrasound measurements, palpation scores), and fate (mortality date and cause, if known). For diet analysis, we used DNA metabarcoding to identify and quantify the relative abundances of plant taxa in 3785 fecal samples from 27 mammal species belonging to 11 families and 7 orders. In all, we recorded 516 food‐plant taxa from at least 87 plant families and 39 orders. For Gorongosa's 15 most common large herbivores, the median sampling depth was 216 fecal samples per species (interquartile range 156–279); the overall median sampling depth was 92 samples per species (range 1–499). We include basic metadata collected in the field (e.g., date, time, GPS location, animal sex, and age) along with laboratory notes and information on plant taxonomic identification. These data are valuable not just as a window on one ecosystem's recovery from armed conflict, but also as a resource for macroecology, meta‐analysis, and synthetic studies of animal movement, diet, and the dynamics of community reassembly. The data are freely available for use and this paper should be cited whenever data are reused; see Data : Metadata : Class III.B.4 for additional details.

Trends in nematocyst abundance provide a mechanism for venom metering in the ‘upside-down’ jellyfish Cassiopea (Cnidaria: Scyphozoa: Rhizostomeae) - Ranko Gacesa; Adrian Jaimes-Becerra; Edgar Gamero-Mora; Steven Lynham; Gabriel Padilla; André C. Morandini; Antonio C. Marques; Paul F. Long (Journal of Experimental Marine Biology and Ecology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Integrating legumes to enhance cereal production: The relative inputs of fertiliser nitrogen and legume biological nitrogen fixation in major wheat and maize producing countries - Mark B. Peoples; Xiaoxi Li; John A. Kirkegaard; Roger D. Armstrong; Ignacio A. Ciampitti; Angelinus C. Franke; Ken E. Giller; James R. Hunt; Marie-Hélène Jeuffroy; Jagdish K. Ladha; Gilles Lemaire; Long Li; et al. (Plant and Soil, 2026)
Background Cereal crops dominate arable agriculture and underpin global food supply. Cereal grain yield is closely related to crop nitrogen (N) uptake. However, excessive inputs of N fertiliser in cereal production systems can have negative environmental consequences and represent high financial risk for farmers. Scope This review explores opportunities to reduce the current reliance of the global staples, wheat ( Triticum aestivum ) and maize ( Zea mays ), on N fertiliser by diversifying cereal-based cropping systems with legumes, in both time (rotation) and space (via intercropping). Increases in cereal grain yield and N uptake resulting from the inclusion of legumes in wheat and maize cropping systems are examined across different geographic regions. The role of grain legumes and legume-based forages, cover-crops and green manures is described for the 15 countries responsible for producing > 70% of the world’s wheat and maize and consuming > 80% of the global applications of N fertiliser to these two cereals. Estimates of the contributions from biological N 2 fixation and legume residual N to cropping soils are provided for individual countries and compared to the N offtake in wheat and maize grain and the quantities of N fertiliser applied. The potential increased area of legumes required for the returns of legume N to match the current amounts of N removed in grain or supplied as fertiliser is assessed for each country, and the strategies that might be necessary to encourage farmers to increase the frequency of legumes used in cereal-dominated cropping systems are outlined.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Medically Tailored Grocery Delivery for Food Pantry Clients with Diabetes - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Brett Rowland; Bonnie Faitak; Jazmin Lane; Rosana Solis-Garcia; Holly C. Felix; Krista Langston; Pearl A. McElfish; Juan Mejia-Otera; et al. (Journal of Nutrition Education and Behavior, 2025)

Zircon U-Pb Ages and Sr-Nd-Hf Isotopes Geochemistry of I-Type Granites in the Jiangda-Weixi Region, Eastern Tibet: Implications for the Tectonic Evolution of the Paleo-Tethyan Orogen - Rui Gao; Tao Wu; Andrew C. Kerr; Han Liu; Long Xiao; Wan Huang (Journal of Earth Science, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Formation of three great Asian plateaus, climate change, and biodiversity - Guan-Long Cao; Xiao-Qian Li; Kun-Li Xiang; Andrey S. Erst; Florian Jabbour; Rosa del C. Ortiz; Jian Yang; Wei Wang (Trends in Ecology & Evolution, 2025)

Nanobubble technology for water treatment: Fundamentals, transformative opportunities, and challenges to full-scale applications - Ashley J. Ansari; Sultan Alharbi; Heriberto Bustamante; Hung C. Duong; Li Gao; Md Abu Hasan Johir; Wenhai Luo; Long D. Nghiem (Journal of Water Process Engineering, 2025)

Diet Quality of School Breakfast and Lunch Menus Across Rural Arkansas - E. Short; S. Sorrell; P. Martin; L. Robinson; K. Bounds; B. Rowland; B. Faitak; C. Long (Journal of the Academy of Nutrition and Dietetics, 2025)

Diet Quality Among Community Members With Diabetes and Food Insecurity in Northwest Arkansas: Comparison Across 3 Racial/Ethnic Groups - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Alexandra Diaz-Cruz; Brett Rowland; Holly C. Felix; Krista Langston; Pearl A. McElfish; Christopher R. Long (Journal of Nutrition Education and Behavior, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Fire severity strongly shapes soil enzyme activities in terrestrial ecosystems: insights from a meta-analysis - Hua Chai; Michelle C. Mack; Jie Li; Guiyao Zhou; Jing Wang; Ruiqiang Liu; Zhenggang Du; Hongyang Chen; Yanghui He; Guang Yang; Long Sun; Xuhui Zhou (Plant and Soil, 2025)

A 3D thermophysical model for binary asteroid systems: Application to the BYORP effect on (175706) 1996 FG3 - Kya C. Sorli; Paul O. Hayne; Rachel H. Cueva; Chloe J. Long; Jay W. McMahon; Daniel J. Scheeres (Icarus, 2025)

Bangong-Nujiang Neo-Tethyan Ocean (Central Tibet): Geodynamics, Crustal Evolution, Metallogeny, and Linkages to the “Yanshan Movement” - Lu-Lu Hao; Wan-Long Hu; Qiang Wang; Andrew C. Kerr; Wei Dan; Xiu-Zheng Zhang; Zong-Yong Yang; Peng Sun (Earth-Science Reviews, 2025)

Omega-3 Fatty Acids and Risk of Ischemic Stroke in REGARDS - Zsuzsanna Ament; Amit Patki; Varun M. Bhave; Naruchorn Kijpaisalratana; Alana C. Jones; Catharine A. Couch; Robert J. Stanton; Pamela M. Rist; Mary Cushman; Suzanne E. Judd; D. Leann Long; M. Ryan Irvin; et al. (Translational Stroke Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Subcutaneous zilucoplan: Evaluation of reproductive toxicology - Marie Lemper; C. Marc Luetjens; Antje Fuchs; Peter Hall; François-Xavier Mathy; Jeff Long; Joy Cavagnaro; Sucharita Roy; Evan A. Thackaberry; Petra Duda (Reproductive Toxicology, 2025)

Modelling of basin-scale nutrient loading variations under the synergistic influences of climate change and socioeconomic development - Chi Zhang; Di Long; Xizhi Nong; Kourosh Behzadian; Dongguo Shao; Luiza C. Campos (Journal of Hydrology, 2025)

Immersive Virtual Reality Dietitian Improves Portion Control Self-Efficacy and Portion Size Estimation Accuracy - Bianca C. Braga; John Long; Sara Maksi; Pejman K. Sajjadi; Alexander Klippel; Travis D. Masterson (Journal of Nutrition Education and Behavior, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Bitter crab disease dynamics in eastern Bering Sea Tanner and snow crab: An underestimated and emergent stressor - Erin J. Fedewa; Pamela C. Jensen; Hamish J. Small; Michael A. Litzow; Michael J. Malick; Leah S. Zacher; W. Christopher Long; Stan Kotwicki (Fisheries Research, 2025)

Evaluating the effects of intrinsic and isolated arabinoxylans on human gut microbiota and short-chain fatty acids: A systematic review and meta-analysis - Changcan Feng; Chenxi Cai; Edward C. Deehan; Shanshan Jiang; Mingyue Yang; Zhongming Weng; Jiahui Long; Guiling Li; Jian Li; Jingwen Liu; Zhengxiao Zhang (Trends in Food Science & Technology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Overexpression of bacterial γ-glutamylcysteine synthetase increases toxic metal(loid)s tolerance and accumulation in Crambe abyssinica - Sudesh Chhikara; Yogita Singh; Stephanie Long; Rakesh Minocha; Craig Musante; Jason C. White; Om Parkash Dhankher (Plant Cell Reports, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Language of Lactation: Decoding RDNs’ Practice Patterns to Enhance Nutrition Care of Breastfeeding Dyads - A. Gaubert; J. Long; L. Woodcock; C. Colin; L. Wright; C. Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2024)

Acetylglutamine Differentially Associated with First-Time Versus Recurrent Stroke - Naruchorn Kijpaisalratana; Zsuzsanna Ament; Amit Patki; Varun M. Bhave; Alana C. Jones; Ana-Lucia Garcia Guarniz; Catharine A. Couch; Mary Cushman; D. Leann Long; M. Ryan Irvin; W. Taylor Kimberly (Translational Stroke Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

From nutrients to fish: Impacts of mesoscale processes in a global CESM-FEISTY eddying ocean model framework - Kristen M. Krumhardt; Matthew C. Long; Colleen M. Petrik; Michael Levy; Frederic S. Castruccio; Keith Lindsay; Lev Romashkov; Anna-Lena Deppenmeier; Rémy Denéchère; Zhuomin Chen; Laura Landrum; Gokhan Danabasoglu; et al. (Progress in Oceanography, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Regular widespread aggregations of the oceanic jellyfish Pelagia noctiluca in the northeast Atlantic over 11 years - A.P. Long; T. Bastian; D. Haberlin; D. Stokes; O. Lyashevska; D. Brophy; C. Lawton; T.K. Doyle (Estuarine, Coastal and Shelf Science, 2024)

Evaluation of a combined drought indicator against crop yield estimations and simulations over the Argentine Humid Pampas - Spennemann Pablo C.; Gustavo Naumann; Mercedes Peretti; Carmelo Cammalleri; Mercedes Salvia; Alessio Bocco; Maria Elena Fernández Long; Martin D. Maas; Hyunglok Kim; Manh-Hung Le; John D. Bolten; Andrea Toreti; et al. (Theoretical and Applied Climatology, 2024)

Walking net $$\dot{V}$$O2 rises with advancing age in older women: where to go from here? - Stephen J. Carter; Harshvardhan Singh; Emily B. Long; Catia Martins; John P. McCarthy; C. Scott Bickel; David R. Bryan; Gary R. Hunter (European Journal of Applied Physiology, 2024)

An assessment of the association between patient characteristics and timely lung cancer treatment - Adam C. Powell; Jeremy T. Pickerell; James W. Long; Bryan A. Loy; Amin J. Mirhadi (Cancer Causes & Control, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Two new species of the deepwater cardinalfish genus Epigonus (Epigonidae) from deep reefs off Curaçao, southern Caribbean - Makoto Okamoto; Carole C. Baldwin; Douglas J. Long (Ichthyological Research, 2024)

Correction to: Using non‑invasive behavioral and physiological data to measure biological age in wild baboons - Chelsea J. Weibel; Mauna R. Dasari; David A. Jansen; Laurence R. Gesquiere; Raphael S. Mututua; J. Kinyua Warutere; Long’ida I. Siodi; Susan C. Alberts; Jenny Tung; Elizabeth A. Archie (GeroScience, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Using non-invasive behavioral and physiological data to measure biological age in wild baboons - Chelsea J. Weibel; Mauna R. Dasari; David A. Jansen; Laurence R. Gesquiere; Raphael S. Mututua; J. Kinyua Warutere; Long’ida I. Siodi; Susan C. Alberts; Jenny Tung; Elizabeth A. Archie (GeroScience, 2024)
Biological aging is near-ubiquitous in the animal kingdom, but its timing and pace vary between individuals and over lifespans. Prospective, individual-based studies of wild animals—especially non-human primates—help identify the social and environmental drivers of this variation by indicating the conditions and exposure windows that affect aging processes. However, measuring individual biological age in wild primates is challenging because several of the most promising methods require invasive sampling. Here, we leverage observational data on behavior and physiology, collected non-invasively from 319 wild female baboons across 2402 female-years of study, to develop a composite predictor of age: the non-invasive physiology and behavior (NPB) clock. We found that age predictions from the NPB clock explained 51% of the variation in females’ known ages. Further, deviations from the clock’s age predictions predicted female survival: females predicted to be older than their known ages had higher adult mortality. Finally, females who experienced harsh early-life conditions were predicted to be about 6 months older than those who grew up in more benign conditions. While the relationship between early adversity and NPB age is noisy, this estimate translates to a predicted 2–3 year reduction in mean adult lifespan in our model. A constraint of our clock is that it is tailored to data collection approaches implemented in our study population. However, many of the clock’s components have analogs in other populations, suggesting that non-invasive data can provide broadly applicable insight into heterogeneity in biological age in natural populations.

Genetic architecture and accuracy of predicted genomic breeding values for sea lice resistance in the St John River aquaculture strain of North American Atlantic salmon - Roger L. Vallejo; Michael R. Pietrak; Melissa M. Milligan; Guangtu Gao; Shogo Tsuruta; Breno O. Fragomeni; Roseanna L. Long; Brian C. Peterson; Yniv Palti (Aquaculture, 2024)

Origin of mafic microgranular enclaves from the Late Triassic Cuojiaoma granitic pluton: Implications for the tectonic evolution of the Yidun arc belt, eastern Tibetan Plateau - Rui Gao; Tao Wu; Andrew C. Kerr; Long Xiao (Journal of Asian Earth Sciences, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Cohesion and shear strength of compacted lunar and Martian regolith simulants - B. Dotson; D. Sanchez Valencia; C. Millwater; P. Easter; J. Long-Fox; D. Britt; P. Metzger (Icarus, 2024)

Removal of NO with Fe(II)NTA solution catalyzed by the carbon treated with ethylenediamine - X.-w. Dou; P.-y. Chen; R.-c. Zhang; X.-li Long (International Journal of Environmental Science and Technology, 2024)

Using down-scan capabilities from recreational-grade side-scan sonar systems to sample paddlefish and evaluate depth use in a reservoir - James M. Long; Patrick Joyce; Lindsey A. Bruckerhoff; Robert C. Lonsinger; Wyatt Wolfenkoehler (Fisheries Research, 2024)

Low temperature selective catalytic oxidation of H2S: Influencing factors, mechanisms and regeneration - Mengxue Yin; Suresh C. Pillai; Nanthi Bolan; Hailong Wang; Hongliang Yin; Zhihao Wu; Yan Zheng; Long Zhao; Feiyue Fan; Hong Hou (Chemical Engineering Journal, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Simulations of ocean deoxygenation in the historical era: insights from forced and coupled models - Yohei Takano; Tatiana Ilyina; Jerry Tjiputra; Yassir A. Eddebbar; Sarah Berthet; Laurent Bopp; Erik Buitenhuis; Momme Butenschön; James R. Christian; John P. Dunne; Matthias Gröger; Hakase Hayashida; et al. (Frontiers in Marine Science, 2023)
Ocean deoxygenation due to anthropogenic warming represents a major threat to marine ecosystems and fisheries. Challenges remain in simulating the modern observed changes in the dissolved oxygen (O 2 ). Here, we present an analysis of upper ocean (0-700m) deoxygenation in recent decades from a suite of the Coupled Model Intercomparison Project phase 6 (CMIP6) ocean biogeochemical simulations. The physics and biogeochemical simulations include both ocean-only (the Ocean Model Intercomparison Project Phase 1 and 2, OMIP1 and OMIP2) and coupled Earth system (CMIP6 Historical) configurations. We examine simulated changes in the O 2 inventory and ocean heat content (OHC) over the past 5 decades across models. The models simulate spatially divergent evolution of O 2 trends over the past 5 decades. The trend (multi-model mean and spread) for upper ocean global O 2 inventory for each of the MIP simulations over the past 5 decades is 0.03 ± 0.39×1014 [mol/decade] for OMIP1, −0.37 ± 0.15×10 14 [mol/decade] for OMIP2, and −1.06 ± 0.68×10 14 [mol/decade] for CMIP6 Historical, respectively. The trend in the upper ocean global O 2 inventory for the latest observations based on the World Ocean Database 2018 is −0.98×10 14 [mol/decade], in line with the CMIP6 Historical multi-model mean, though this recent observations-based trend estimate is weaker than previously reported trends. A comparison across ocean-only simulations from OMIP1 and OMIP2 suggests that differences in atmospheric forcing such as surface wind explain the simulated divergence across configurations in O 2 inventory changes. Additionally, a comparison of coupled model simulations from the CMIP6 Historical configuration indicates that differences in background mean states due to differences in spin-up duration and equilibrium states result in substantial differences in the climate change response of O 2 . Finally, we discuss gaps and uncertainties in both ocean biogeochemical simulations and observations and explore possible future coordinated ocean biogeochemistry simulations to fill in gaps and unravel the mechanisms controlling the O 2 changes.

Tectonically assisted emplacement of oceanic intraplate volcanoes: The Bathymetrists Seamounts, central Atlantic - Froukje M. van der Zwan; Nico Augustin; Morgane Le Saout; Elisabeth Seidel; Anne-C. Wölfl; Martin Schade; Danai Lampridou; Xiaojun Long; Jörg Follmann; Jakub Miluch; Janto Schönberg; Richard J. Antonio; et al. (Geomorphology, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Tree species richness around urban red maples reduces pest density but does not enhance biological control - Caleb J. Wilson; Kristi M. Backe; Michael G. Just; Eleanor C. Lahr; Annemarie M. Nagle; Lawrence C. Long; Adam G. Dale; Steven D. Frank (Urban Forestry & Urban Greening, 2023)

Viability of side-scan sonar to enumerate Paddlefish, a large pelagic freshwater fish, in rivers and reservoirs - Wyatt Wolfenkoehler; James M. Long; Ryan Gary; Richard A. Snow; Jason D. Schooley; Lindsey A. Bruckerhoff; Robert C. Lonsinger (Fisheries Research, 2023)

Trends in soil moisture content and water deficits in Argentina and the role of climate contribution - M. Peretti; P. C. Spennemann; M. E. Fernández Long (Theoretical and Applied Climatology, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Comparative assessment of energy generation from ammonia oxidation by different functional bacterial communities - Vitor Cano; Marcelo A. Nolasco; Halil Kurt; Chenghua Long; Julio Cano; Sabrina C. Nunes; Kartik Chandran (Science of The Total Environment, 2023)

Catchment sourcing urban pesticide pollution using constructed wetlands in Melbourne, Australia - V. Pettigrove; K. Hassell; C. Kellar; S. Long; D. MacMahon; J. Myers; H. Nguyen; M. Walpitagama (Science of The Total Environment, 2023)

Mechanisms of individual variation in large herbivore diets: Roles of spatial heterogeneity and state‐dependent foraging - Reena H. Walker; Matthew C. Hutchinson; Arjun B. Potter; Justine A. Becker; Ryan A. Long; Robert M. Pringle (Ecology, 2023)
Many populations of consumers consist of relatively specialized individuals that eat only a subset of the foods consumed by the population at large. Although the ecological significance of individual‐level diet variation is recognized, such variation is difficult to document, and its underlying mechanisms are poorly understood. Optimal foraging theory provides a useful framework for predicting how individuals might select different diets, positing that animals balance the “opportunity cost” of stopping to eat an available food item against the cost of searching for something more nutritious; diet composition should be contingent on the distribution of food, and individual foragers should be more selective when they have greater energy reserves to invest in searching for high‐quality foods. We tested these predicted mechanisms of individual niche differentiation by quantifying environmental (resource heterogeneity) and organismal (nutritional condition) determinants of diet in a widespread browsing antelope (bushbuck, Tragelaphus sylvaticus ) in an African floodplain‐savanna ecosystem. We quantified individuals' realized dietary niches (taxonomic richness and composition) using DNA metabarcoding of fecal samples collected repeatedly from 15 GPS‐collared animals (range 6–14 samples per individual, median 12). Bushbuck diets were structured by spatial heterogeneity and constrained by individual condition. We observed significant individual‐level partitioning of food plants by bushbuck both within and between two adjacent habitat types (floodplain and woodland). Individuals with home ranges that were closer together and/or had similar vegetation structure (measured using LiDAR) ate more similar diets, supporting the prediction that heterogeneous resource distribution promotes individual differentiation. Individuals in good nutritional condition had significantly narrower diets (fewer plant taxa), searched their home ranges more intensively (intensity‐of‐use index), and had higher‐quality diets (percent digestible protein) than those in poor condition, supporting the prediction that animals with greater endogenous reserves have narrower realized niches because they can invest more time in searching for nutritious foods. Our results support predictions from optimal foraging theory about the energetic basis of individual‐level dietary variation and provide a potentially generalizable framework for understanding how individuals' realized niche width is governed by animal behavior and physiology in heterogeneous landscapes.

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Soil moisture estimates over sporadically flooded farmlands: synergies and biases of remote sensing and in situ sources - Lucía M. Cappelletti; Anna A. Sörensson; Mercedes Salvia; Romina C. Ruscica; Pablo Spennemann; Maria E. Fernandez-Long; Esteban Jobbágy (International Journal of Remote Sensing, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Climate drivers of Southern Ocean phytoplankton community composition and potential impacts on higher trophic levels - Kristen M. Krumhardt; Matthew C. Long; Zephyr T. Sylvester; Colleen M. Petrik (Frontiers in Marine Science, 2022)
Southern Ocean phytoplankton production supports rich Antarctic marine ecosystems comprising copepods, krill, fish, seals, penguins, and whales. Anthropogenic climate change, however, is likely to drive rearrangements in phytoplankton community composition with potential ramifications for the whole ecosystem. In general, phytoplankton communities dominated by large phytoplankton, i.e., diatoms, yield shorter, more efficient food chains than ecosystems supported by small phytoplankton. Guided by a large ensemble of Earth system model simulations run under a high emission scenario (RCP8.5), we present hypotheses for how anthropogenic climate change may drive shifts in phytoplankton community structure in two regions of the Southern Ocean: the Antarctic Circumpolar Current (ACC) region and the sea ice zone (SIZ). Though both Southern Ocean regions experience warmer ocean temperatures and increased advective iron flux under 21st century climate warming, the model simulates a proliferation of diatoms at the expense of small phytoplankton in the ACC, while the opposite patterns are evident in the SIZ. The primary drivers of simulated diatom increases in the ACC region include warming, increased iron supply, and reduced light from increased cloudiness. In contrast, simulated reductions in ice cover yield greater light penetration in the SIZ, generating a phenological advance in the bloom accompanied by a shift to more small phytoplankton that effectively consume available iron; the result is an overall increase in net primary production, but a decreasing proportion of diatoms. Changes of this nature may promote more efficient trophic energy transfer via copepods or krill in the ACC region, while ecosystem transfer efficiency in the SIZ may decline as small phytoplankton grow in dominance, possibly impacting marine food webs sustaining Antarctic marine predators. Despite the simplistic ecosystem representation in our model, our results point to a potential shift in the relative success of contrasting phytoplankton ecological strategies in different regions of the Southern Ocean, with ramifications for higher trophic levels.

Senolytic treatment rescues blunted muscle hypertrophy in old mice - Cory M. Dungan; Vandre C. Figueiredo; Yuan Wen; Georgia L. VonLehmden; Christopher J. Zdunek; Nicholas T. Thomas; C. Brooks Mobley; Kevin A. Murach; Camille R. Brightwell; Douglas E. Long; Christopher S. Fry; Philip A. Kern; et al. (GeroScience, 2022)
With aging, skeletal muscle plasticity is attenuated in response to exercise. Here, we report that senescent cells, identified using senescence-associated β-galactosidase (SA β-Gal) activity and p21 immunohistochemistry, are very infrequent in resting muscle, but emerge approximately 2 weeks after a bout of resistance exercise in humans. We hypothesized that these cells contribute to blunted hypertrophic potential in old age. Using synergist ablation-induced mechanical overload (MOV) of the plantaris muscle to model resistance training in adult (5–6-month) and old (23–24-month) male C57BL/6 J mice, we found increased senescent cells in both age groups during hypertrophy. Consistent with the human data, there were negligible senescent cells in plantaris muscle from adult and old sham controls, but old mice had significantly more senescent cells 7 and 14 days following MOV relative to young. Old mice had blunted whole-muscle hypertrophy when compared to adult mice, along with smaller muscle fibers, specifically glycolytic type 2x + 2b fibers. To ablate senescent cells using a hit-and-run approach, old mice were treated with vehicle or a senolytic cocktail consisting of 5 mg/kg dasatinib and 50 mg/kg quercetin (D + Q) on days 7 and 10 during 14 days of MOV; control mice underwent sham surgery with or without senolytic treatment. Old mice given D + Q had larger muscles and muscle fibers after 14 days of MOV, fewer senescent cells when compared to vehicle-treated old mice, and changes in the expression of genes (i.e., Igf1 , Ddit4 , Mmp14 ) that are associated with hypertrophic growth. Our data collectively show that senescent cells emerge in human and mouse skeletal muscle following a hypertrophic stimulus and that D + Q improves muscle growth in old mice.

Assessment of potential selection bias in neuroimaging studies of postoperative delirium and cognitive decline: lessons from the SAGES study - Michele Cavallari; Tamara G. Fong; Alexandra Touroutoglou; Bradford C. Dickerson; Eva Schmitt; Thomas G. Travison; Edward R. Marcantonio; Long H. Ngo; Towia Libermann; Alvaro Pascual-Leone; Mouhsin M. Shafi; Sharon K. Inouye; et al. (Brain Imaging and Behavior, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Vanguard Russet: A Fresh Market Potato Cultivar with Medium-Early Maturity and Long Dormancy - M. I. Vales; D. C. Scheuring; J. W. Koym; D. G. Holm; S. Y. C. Essah; R. G. Wilson; J. K. Sidhu; R. G. Novy; J. L. Whitworth; J. C. Stark; R. R. Spear; V. Sathuvalli; et al. (American Journal of Potato Research, 2022)

Multi-donor × elite-based populations reveal QTL for low-lodging wheat - M. Fernanda Dreccer; Bethany Macdonald; Claire A. Farnsworth; M. Valeria Paccapelo; Mary Anne Awasi; Anthony G. Condon; Kerrie Forrest; Ian Lee Long; C. Lynne McIntyre (Theoretical and Applied Genetics, 2022)
Key message Low-lodging high-yielding wheat germplasm and SNP-tagged novel alleles for lodging were identified in a process that involved selecting donors through functional phenotyping for underlying traits with a designed phenotypic screen, and a crossing strategy involving multiple-donor × elite populations. Abstract Lodging is a barrier to achieving high yield in wheat. As part of a study investigating the potential to breed low-lodging high-yielding wheat, populations were developed crossing four low-lodging high-yielding donors selected based on lodging related traits, with three cultivars. Lodging was evaluated in single rows in an early generation and subsequently in plots in 2 years with contrasting lodging environment. A large number of lines lodged less than their recurrent parents, and some were also higher yielding. Heritability for lodging was high, but the genetic correlation between contrasting environments was intermediate-low. Lodging genotypic rankings in single rows did not correlate well with plots. Populations from the highest lodging background were genotyped (90 K iSelect BeadChip array). Fourteen markers on nine chromosomes were associated with lodging, differing under high- versus low-lodging conditions. Of the fourteen markers, ten were found to co-locate with previously identified QTL for lodging-related traits or at homoeologous locations for previously identified lodging-related QTL, while the remaining four markers (in chromosomes 2D, 4D, 7B and 7D) appear to map to novel QTL for lodging. Lines with more favourable markers lodged less, suggesting value in these markers as a selection tool. This study demonstrates that the combination of donor functional phenotyping, screen design and crossing strategy can help identify novel alleles in germplasm without requiring extensive bi-parental populations.

Coupling and coordination of China's economy, ecological environment and health from a green production perspective - C. Hou; H. Chen; R. Long (International Journal of Environmental Science and Technology, 2022)

Detecting climate signals in populations across life histories - Stéphanie Jenouvrier; Matthew C. Long; Christophe F. D. Coste; Marika Holland; Marlène Gamelon; Nigel G. Yoccoz; Bernt‐Erik Sæther (Global Change Biology, 2022)
Climate impacts are not always easily discerned in wild populations as detecting climate change signals in populations is challenged by stochastic noise associated with natural climate variability, variability in biotic and abiotic processes, and observation error in demographic rates. Detection of the impact of climate change on populations requires making a formal distinction between signals in the population associated with long‐term climate trends from those generated by stochastic noise. The time of emergence (ToE) identifies when the signal of anthropogenic climate change can be quantitatively distinguished from natural climate variability. This concept has been applied extensively in the climate sciences, but has not been explored in the context of population dynamics. Here, we outline an approach to detecting climate‐driven signals in populations based on an assessment of when climate change drives population dynamics beyond the envelope characteristic of stochastic variations in an unperturbed state. Specifically, we present a theoretical assessment of the time of emergence of climate‐driven signals in population dynamics ( ). We identify the dependence of on the magnitude of both trends and variability in climate and also explore the effect of intrinsic demographic controls on . We demonstrate that different life histories (fast species vs. slow species), demographic processes (survival, reproduction), and the relationships between climate and demographic rates yield population dynamics that filter climate trends and variability differently. We illustrate empirically how to detect the point in time when anthropogenic signals in populations emerge from stochastic noise for a species threatened by climate change: the emperor penguin. Finally, we propose six testable hypotheses and a road map for future research.

Characterisation of teaghrelin-like principles from Assam tea cultivated in Thailand - Yue-Chiun Li; Chutima Tanapichatsakul; Patcharee Pripdeevech; Tsong Long Hwang; Ping-Chung Kuo; Jason T. C. Tzen (Natural Product Research, 2022)

Effects of chemical cues from two piscine predators, natal predator regime, and time since cue introduction, on the movements of aquatic isopods (Caecidotea communis) - Elizabeth C. Long; Erika V. Iyengar (Hydrobiologia, 2022)

Comparison of Observations and Predictions of Daytime Planetary-Boundary-Layer Heights and Surface Meteorological Variables in the Columbia River Gorge and Basin During the Second Wind Forecast Improvement Project - Laura Bianco; P. Muradyan; I. Djalalova; J. M. Wilczak; J. B. Olson; J. S. Kenyon; R. Kotamarthi; K. Lantz; C. N. Long; D. D. Turner (Boundary-Layer Meteorology, 2022)
The second Wind Forecast Improvement Project (WFIP2) is an 18-month field campaign in the Pacific Northwest U.S.A., whose goal is to improve the accuracy of numerical-weather-prediction forecasts in complex terrain. The WFIP2 campaign involved the deployment of a large suite of in situ and remote sensing instrumentation, including eight 915-MHz wind-profiling radars, and surface meteorological stations. The evolution and annual variability of the daytime convective planetary-boundary-layer (PBL) height is investigated using the wind-profiling radars. Three models with different horizontal grid spacing are evaluated: the Rapid Refresh, the High-Resolution Rapid Refresh, and its nested version. The results are used to assess errors in the prediction of PBL height within the experimental and control versions of the models, with the experimental versions including changes and additions to the model parametrizations developed during the field campaign, and the control version using the parametrizations present in the National Oceanic and Atmospheric Administration/National Centers for Environmental Prediction operational version of the models at the start of the project. Results show that the high-resolution models outperform the low-resolution versions, the experimental versions perform better compared with the control versions, model PBL height estimations are more accurate on cloud-free days, and model estimates of the PBL height growth rate are more accurate than model estimates of the rate of decay. Finally, using surface sensors, we assess surface meteorological variables, finding improved surface irradiance and, to a lesser extent, improved 2-m temperature in the experimental version of the model.

Estimating Bycatch Mortality for Marine Mammals: Concepts and Best Practices - Jeffrey E. Moore; Dennis Heinemann; Tessa B. Francis; Philip S. Hammond; Kristy J. Long; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli A. Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Fisheries bycatch is the greatest current source of human-caused deaths of marine mammals worldwide, with severe impacts on the health and viability of many populations. Recent regulations enacted in the United States under the Fish and Fish Product Import Provisions of its Marine Mammal Protection Act require nations with fisheries exporting fish and fish products to the United States (hereafter, “export fisheries”) to have or establish marine mammal protection standards that are comparable in effectiveness to the standards for United States commercial fisheries. In many cases, this will require estimating marine mammal bycatch in those fisheries. Bycatch estimation is conceptually straightforward but can be difficult in practice, especially if resources (funding) are limiting or for fisheries consisting of many, small vessels with geographically-dispersed landing sites. This paper describes best practices for estimating bycatch mortality, which is an important ingredient of bycatch assessment and mitigation. We discuss a general bycatch estimator and how to obtain its requisite bycatch-rate and fisheries-effort data. Scientific observer programs provide the most robust bycatch estimates and consequently are discussed at length, including characteristics such as study design, data collection, statistical analysis, and common sources of estimation bias. We also discuss alternative approaches and data types, such as those based on self-reporting and electronic vessel-monitoring systems. This guide is intended to be useful to managers and scientists in countries having or establishing programs aimed at managing marine mammal bycatch, especially those conducting first-time assessments of fisheries impacts on marine mammal populations.

Effects of Infectious Diseases on Population Dynamics of Marine Organisms in Chesapeake Bay - Jerelle A. Jesse; M. Victoria Agnew; Kohma Arai; C. Taylor Armstrong; Shannon M. Hood; Mariah L. Kachmar; Jessie T. Long; Alexandra J. McCarty; Morgan O. Ross; Kasondra D. Rubalcava; Jacob Shaner; Sakura Tanaka; et al. (Estuaries and Coasts, 2021)
Diseases are important drivers of population and ecosystem dynamics. This review synthesizes the effects of infectious diseases on the population dynamics of nine species of marine organisms in the Chesapeake Bay. Diseases generally caused increases in mortality and decreases in growth and reproduction. Effects of diseases on eastern oyster ( Crassostrea virginica ) appear to be low in the 2000s compared to effects in the 1980s–1990s. However, the effects of disease were not well monitored for most of the diseases in marine organisms of the Chesapeake Bay, and few studies considered effects on growth and reproduction. Climate change and other anthropogenic effects are expected to alter host-pathogen dynamics, with diseases of some species expected to worsen under predicted future conditions (e.g., increased temperature). Additional study of disease prevalence, drivers of disease, and effects on population dynamics could improve fisheries management and forecasting of climate change effects on marine organisms in the Chesapeake Bay.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Best Practices for Assessing and Managing Bycatch of Marine Mammals - Paul R. Wade; Kristy J. Long; Tessa B. Francis; André E. Punt; Philip S. Hammond; Dennis Heinemann; Jeffrey E. Moore; Randall R. Reeves; Maritza Sepúlveda; Genoa Sullaway; Guðjón Már Sigurðsson; Margaret C. Siple; et al. (Frontiers in Marine Science, 2021)
Bycatch in marine fisheries is the leading source of human-caused mortality for marine mammals, has contributed to substantial declines of many marine mammal populations and species, and the extinction of at least one. Schemes for evaluating marine mammal bycatch largely rely on estimates of abundance and bycatch, which are needed for calculating biological reference points and for determining conservation status. However, obtaining these estimates is resource intensive and takes careful long-term planning. The need for assessments of marine mammal bycatch in fisheries is expected to increase worldwide due to the recently implemented Import Provisions of the United States Marine Mammal Protection Act. Managers and other stakeholders need reliable, standardized methods for collecting data to estimate abundance and bycatch rates. In some cases, managers will be starting with little or no data and no system in place to collect data. We outline a comprehensive framework for managing bycatch of marine mammals. We describe and provide guidance on (1) planning for an assessment of bycatch, (2) collecting appropriate data (e.g., abundance and bycatch estimates), (3) assessing bycatch and calculating reference points, and (4) using the results of the assessment to guide marine mammal bycatch reduction. We also provide a brief overview of available mitigation techniques to reduce marine mammal bycatch in various fisheries. This paper provides information for scientists and resource managers in the hope that it will lead to new or improved programs for assessing marine mammal bycatch, establishing best practices, and enhancing marine mammal conservation globally.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Estimating the Abundance of Marine Mammal Populations - Philip S. Hammond; Tessa B. Francis; Dennis Heinemann; Kristy J. Long; Jeffrey E. Moore; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Motivated by the need to estimate the abundance of marine mammal populations to inform conservation assessments, especially relating to fishery bycatch, this paper provides background on abundance estimation and reviews the various methods available for pinnipeds, cetaceans and sirenians. We first give an “entry-level” introduction to abundance estimation, including fundamental concepts and the importance of recognizing sources of bias and obtaining a measure of precision. Each of the primary methods available to estimate abundance of marine mammals is then described, including data collection and analysis, common challenges in implementation, and the assumptions made, violation of which can lead to bias. The main method for estimating pinniped abundance is extrapolation of counts of animals (pups or all-ages) on land or ice to the whole population. Cetacean and sirenian abundance is primarily estimated from transect surveys conducted from ships, small boats or aircraft. If individuals of a species can be recognized from natural markings, mark-recapture analysis of photo-identification data can be used to estimate the number of animals using the study area. Throughout, we cite example studies that illustrate the methods described. To estimate the abundance of a marine mammal population, key issues include: defining the population to be estimated, considering candidate methods based on strengths and weaknesses in relation to a range of logistical and practical issues, being aware of the resources required to collect and analyze the data, and understanding the assumptions made. We conclude with a discussion of some practical issues, given the various challenges that arise during implementation.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Dating deformation using sheared leucogranite: temporal constraints by 40Ar/39Ar thermochronology for the Mae Ping shear zone, NW Thailand - Yu-Ling Lin; Tung-Yi Lee; Ching-Hua Lo; Sarah C. Sherlock; Yoshiyuki Iizuka; Tadashi Usuki; Long Xiang Quek; Punya Charusiri (Contributions to Mineralogy and Petrology, 2021)

Online Information for Treatment for Low-Risk Thyroid Cancer: Assessment of Timeliness, Content, Quality, and Readability - Amanda R. Doubleday; Sherwin Novin; Kristin L. Long; David F. Schneider; Rebecca S. Sippel; Susan C. Pitt (Journal of Cancer Education, 2021)

Antibacterial Performance of a Streptomyces spectabilis Strain Producing Metacycloprodigiosin - L. I. Meng-xi; Huang Hui-bin; Long Jie-yun; C. A. O. Jing-xiao; Zhang Zhen-wang (Current Microbiology, 2021)

Detecting Climate Signals in Southern Ocean Krill Growth Habitat - Zephyr T. Sylvester; Matthew C. Long; Cassandra M. Brooks (Frontiers in Marine Science, 2021)
Climate change is rapidly altering the habitat of Antarctic krill ( Euphausia superba ), a key species of the Southern Ocean food web. Krill are a critical element of Southern Ocean ecosystems as well as biogeochemical cycles, while also supporting an international commercial fishery. In addition to trends forced by global-scale, human-driven warming, the Southern Ocean is highly dynamic, displaying large fluctuations in surface climate on interannual to decadal timescales. The dual roles of forced climate change and natural variability affecting Antarctic krill habitat, and therefore productivity, complicate interplay of observed trends and contribute to uncertainty in future projections. We use the Community Earth System Model Large Ensemble (CESM-LE) coupled with an empirically derived model of krill growth to detect and attribute trends associated with “forced,” human-driven climate change, distinguishing these from variability arising naturally. The forced trend in krill growth is characterized by a poleward contraction of optimal conditions and an overall reduction in Southern Ocean krill habitat. However, the amplitude of natural climate variability is relatively large, such that the forced trend cannot be formally distinguished from natural variability at local scales over much of the Southern Ocean by 2100. Our results illustrate how natural variability is an important driver of regional krill growth trends and can mask the forced trend until late in the 21st century. Given the ecological and commercial global importance of krill, this research helps inform current and future Southern Ocean krill management in the context of climate variability and change.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Sea-trial verification of a novel system for monitoring biofouling and testing anti-fouling coatings in highly energetic environments targeted by the marine renewable energy industry - Andrew Want; Michael C. Bell; Robert E. Harris; Mark Q. Hull; Caitlin R. Long; Joanne S. Porter (Biofouling, 2021)

Assessing the Skill of a High-Resolution Marine Biophysical Model Using Geostatistical Analysis of Mesoscale Ocean Chlorophyll Variability From Field Observations and Remote Sensing - Rachel Eveleth; David M. Glover; Matthew C. Long; Ivan D. Lima; Alison P. Chase; Scott C. Doney (Frontiers in Marine Science, 2021)
High-resolution ocean biophysical models are now routinely being conducted at basin and global-scale, opening opportunities to deepen our understanding of the mechanistic coupling of physical and biological processes at the mesoscale. Prior to using these models to test scientific questions, we need to assess their skill. While progress has been made in validating the mean field, little work has been done to evaluate skill of the simulated mesoscale variability. Here we use geostatistical 2-D variograms to quantify the magnitude and spatial scale of chlorophyll a patchiness in a 1/10th-degree eddy-resolving coupled Community Earth System Model simulation. We compare results from satellite remote sensing and ship underway observations in the North Atlantic Ocean, where there is a large seasonal phytoplankton bloom. The coefficients of variation, i.e., the arithmetic standard deviation divided by the mean, from the two observational data sets are approximately invariant across a large range of mean chlorophyll a values from oligotrophic and winter to subpolar bloom conditions. This relationship between the chlorophyll a mesoscale variability and the mean field appears to reflect an emergent property of marine biophysics, and the high-resolution simulation does poorly in capturing this skill metric, with the model underestimating observed variability under low chlorophyll a conditions such as in the subtropics.

Associations of muscle lipid content with physical function and resistance training outcomes in older adults: altered responses with metformin - Douglas E. Long; Bailey D. Peck; Steven C. Tuggle; Alejandro G. Villasante Tezanos; Samuel T. Windham; Marcas M. Bamman; Philip A. Kern; Charlotte A. Peterson; Rosicka G. Walton (GeroScience, 2021)

Icariin reduces bone loss in a Rankl‐induced transgenic medaka ( Oryzias latipes ) model for osteoporosis - Cuong V. Pham; Thanh T. Pham; Thuy T. Lai; Dat C. Trinh; Huong V. M. Nguyen; Tam T. M. Ha; Thuong T. Phuong; Long D. Tran; Christoph Winkler; Thuy T. To (Journal of Fish Biology, 2021)
Given the limitations and side effects of many synthetic drugs, natural products are an important alternative source for drugs and medications for many diseases. Icariin (ICA), one of the main flavonoids from plants of the Epimedium genus, has been shown to ameliorate osteoporosis and improve bone health in preclinical studies. Those studies have used different in vivo models, mostly rodents, but the underlying mechanisms remain unclear. The present study shows, for the first time, that ICA reduces bone damage in a Rankl‐induced medaka fish ( Oryzias latipes ), a non‐rodent osteoporosis model. Live imaging was previously performed in this model to characterize antiresorptive and bone‐anabolic properties of drugs. Here, a new quantification method (I M ) was established based on the length of mineralized neural arches to quantify levels of bone mineralization damage and protection in early post‐embryonic fish. This method was validated by quantification of three levels of bone damage in three independent Rankl fish lines, and by the determination of different degrees of severity of osteoporosis‐like phenotypes in one Rankl line exposed to variable Rankl induction schemes. I M was also used to quantify the efficacy of alendronate and etidronate, two common anti‐osteoporotic bisphosphonates, and revealed comparable bone protective effects for ICA and alendronate in this fish osteoporosis model. This study's data support the value of the medaka fish model for bone research and establish a method to screen for novel osteoprotective compounds.

Gender Role, But Not Sex, Shapes Humans’ Susceptibility to Emotion - Jiajin Yuan; Hong Li; Quanshan Long; Jiemin Yang; Tatia M. C. Lee; Dandan Zhang (Neuroscience Bulletin, 2021)

Precise U–Pb baddeleyite dating of the Derim Derim Dolerite, McArthur Basin, Northern Territory: old and new SHRIMP and ID-TIMS constraints - S. Bodorkos; J. L. Crowley; J. C. Claoué-Long; J. R. Anderson; C. W. Magee (Australian Journal of Earth Sciences, 2021)

On the control of subantarctic stratification by the ocean circulation - R. Justin Small; Alice K. DuVivier; Daniel B. Whitt; Matthew C. Long; Ian Grooms; William G. Large (Climate Dynamics, 2021)

Increased time sampling in an evolve‐and‐resequence experiment with outcrossing Saccharomyces cerevisiae reveals multiple paths of adaptive change - Mark A. Phillips; Ian C. Kutch; Anthony D. Long; Molly K. Burke (Molecular Ecology, 2020)
“Evolve and resequence” (E&R) studies combine experimental evolution and whole‐genome sequencing to interrogate the genetics underlying adaptation. Due to ease of handling, E&R work with asexual organisms such as bacteria can employ optimized experimental design, with large experiments and many generations of selection. By contrast, E&R experiments with sexually reproducing organisms are more difficult to implement, and design parameters vary dramatically among studies. Thus, efforts have been made to assess how these differences, such as number of independent replicates, or size of experimental populations, impact inference. We add to this work by investigating the role of time sampling—the number of discrete time points sequence data are collected from evolving populations. Using data from an E&R experiment with outcrossing Saccharomyces cerevisiae in which populations were sequenced 17 times over ~540 generations, we address the following questions: (a) Do more time points improve the ability to identify candidate regions underlying selection? And (b) does high‐resolution sampling provide unique insight into evolutionary processes driving adaptation? We find that while time sampling does not improve the ability to identify candidate regions, high‐resolution sampling does provide valuable opportunities to characterize evolutionary dynamics. Increased time sampling reveals three distinct trajectories for adaptive alleles: one consistent with classic population genetic theory (i.e., models assuming constant selection coefficients), and two where trajectories suggest more context‐dependent responses (i.e., models involving dynamic selection coefficients). We conclude that while time sampling has limited impact on candidate region identification, sampling eight or more time points has clear benefits for studying complex evolutionary dynamics.

Identification of quantitative trait loci governing early germination and seedling vigor traits related to weed competitive ability in rice - Niña Gracel B. Dimaano; Jauhar Ali; Anumalla Mahender; Pompe C. Sta. Cruz; Aurora M. Baltazar; Maria Genaleen Q. Diaz; Yun Long Pang; Bart L. Acero; Zhikang Li (Euphytica, 2020)
Weed competitive ability (WCA) is vital for the improvement of grain yield under direct-seeded and aerobic rice ecosystems where weeds are a major limiting factor. Early seed germination (ESG) and early seedling vigor (ESV) are the crucial traits for WCA. This study attempted to map the quantitative trait loci (QTLs) and hotspot regions governing ESG and ESV traits. A total of 167 BC 1 F 5 selective introgression lines developed from an early backcross population involving Weed Tolerant Rice 1 (WTR-1) as the recipient parent and Y-134 as the donor parent were phenotyped for ESG and ESV traits. Analysis of variance revealed significant differences in ESG-related traits except for root length and in ESV-related traits except for plant height at 7 days after sowing. A total of 677-high quality single nucleotide polymorphism (SNP) markers were used to analyze the marker-trait association from a 6 K SNP genotyping array. Forty-three QTLs were identified on all chromosomes, except on chromosomes 4 and 8. Thirty QTLs were contributed by a desirable allele from Y-134, whereas 13 QTLs were from WTR-1. Twenty-eight of the identified genetic loci associated with ESG and ESV traits were novel. Two QTL hotspot regions were mapped on chromosomes 11 and 12. The genomic regions of QTL hotspots were fine-tuned and a total of 13 putative candidate genes were discovered on chromosomes 11 and 12 collectively. The mapped QTLs will be useful in advancing the marker aided-selection schemes and breeding programs for the development of rice cultivars with WCA traits.

Correction to: Complex patterns of genetic and morphological differentiation in the Smallmouth Bass subspecies (Micropterus dolomieu dolomieu and M. d. velox) of the Central Interior Highlands - Joe C. Gunn; Leah K. Berkman; Jeff Koppelman; Andrew T. Taylor; Shannon Brewer; James M. Long; Lori S. Eggert (Conservation Genetics, 2020)

Complex patterns of genetic and morphological differentiation in the Smallmouth Bass subspecies (Micropterus dolomieu dolomieu and M. d. velox) of the Central Interior Highlands - Joe C. Gunn; Leah K. Berkman; Jeff Koppelman; Andrew T. Taylor; Shannon Brewer; James M. Long; Lori S. Eggert (Conservation Genetics, 2020)

Nociceptive related microRNAs and their role in rheumatoid arthritis - S. Reyes-Long; J. L. Cortes-Altamirano; D. Clavijio-Cornejo; M. Gutiérrez; C. Bertolazzi; C. Bandala; C. Pineda; A. Alfaro-Rodríguez (Molecular Biology Reports, 2020)

Management of Enteric Methanogenesis in Ruminants by Algal-Derived Feed Additives - Janice I. McCauley; Leen Labeeuw; Ana C. Jaramillo-Madrid; Luong N. Nguyen; Long D. Nghiem; Alex V. Chaves; Peter J. Ralph (Current Pollution Reports, 2020)

Tracking Improvement in Simulated Marine Biogeochemistry Between CMIP5 and CMIP6 - Roland Séférian; Sarah Berthet; Andrew Yool; Julien Palmiéri; Laurent Bopp; Alessandro Tagliabue; Lester Kwiatkowski; Olivier Aumont; James Christian; John Dunne; Marion Gehlen; Tatiana Ilyina; et al. (Current Climate Change Reports, 2020)
Purpose of Review The changes or updates in ocean biogeochemistry component have been mapped between CMIP5 and CMIP6 model versions, and an assessment made of how far these have led to improvements in the simulated mean state of marine biogeochemical models within the current generation of Earth system models (ESMs). Recent Findings The representation of marine biogeochemistry has progressed within the current generation of Earth system models. However, it remains difficult to identify which model updates are responsible for a given improvement. In addition, the full potential of marine biogeochemistry in terms of Earth system interactions and climate feedback remains poorly examined in the current generation of Earth system models. Summary Increasing availability of ocean biogeochemical data, as well as an improved understanding of the underlying processes, allows advances in the marine biogeochemical components of the current generation of ESMs. The present study scrutinizes the extent to which marine biogeochemistry components of ESMs have progressed between the 5th and the 6th phases of the Coupled Model Intercomparison Project (CMIP).

A novel hydrogel for highly efficient adsorption of Cu(II): synthesis, characterization, and mechanisms - Jun Wan; Lin Chen; Qiang Li; Yuxuan Ye; Xiaonan Feng; Aijiao Zhou; Xuejun Long; Dongsheng Xia; Tian C. Zhang (Environmental Science and Pollution Research, 2020)

Risk of bird predation and defoliating insect abundance are greater in urban forest fragments than street trees - Lawrence C. Long; Steven D. Frank (Urban Ecosystems, 2020)

Rapid assessment of management options for promoting stock rebuilding in data‐poor species under climate change - Jonathan C. P. Reum; P. Sean McDonald; W. Christopher Long; Kirstin K. Holsman; Lauren Divine; David Armstrong; Jan Armstrong (Conservation Biology, 2020)
The development of species recovery plans requires considering likely outcomes of different management interventions, but the complicating effects of climate change are rarely evaluated. We examined how qualitative network models (QNMs) can be deployed to support decision making when data, time, and funding limitations restrict use of more demanding quantitative methods. We used QNMs to evaluate management interventions intended to promote the rebuilding of a collapsed stock of blue king crab (Paralithodes platypus) (BKC) around the Pribilof Islands (eastern Bering Sea) to determine how their potential efficacy may change under climate change. Based on stakeholder input and a literature review, we constructed a QNM that described the life cycle of BKC, key ecological interactions, potential climate‐change impacts, relative interaction strengths, and uncertainty in terms of interaction strengths and link presence. We performed sensitivity analyses to identify key sources of prediction uncertainty. Under a scenario of no climate change, predicted increases in BKC were reliable only when stock enhancement was implemented in a BKC hatchery‐program scenario. However, when climate change was accounted for, the intervention could not counteract its adverse impacts, which had an overall negative effect on BKC. The remaining management scenarios related to changes in fishing effort on BKC predators. For those scenarios, BKC outcomes were unreliable, but climate change further decreased the probability of observing recovery. Including information on relative interaction strengths increased the likelihood of predicting positive outcomes for BKC approximately 5–50% under the management scenarios. The largest gains in prediction precision will be made by reducing uncertainty associated with ecological interactions between adult BKC and red king crab (Paralithodes camtschaticus). Qualitative network models are useful options when data are limited, but they remain underutilized in conservation.

Corrigendum: Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Bo Yang; Emmanuel S. Boss; Nils Haëntjens; Matthew C. Long; Michael J. Behrenfeld; Rachel Eveleth; Scott C. Doney (Frontiers in Marine Science, 2020)

Racial/Ethnic Differences in Comprehension of Biospecimen Collection: a Nationwide University of Rochester Cancer Center NCI Community Oncology Research Program Study - Matthew Asare; Charles E. Heckler; Eva Culakova; Charles S. Kamen; Amber S. Kleckner; Lori M. Minasian; David S. Wendler; Michelle Feige; Carol J. Weil; Joan Long; Sharon K. Cole; Adedayo A. Onitilo; et al. (Journal of Cancer Education, 2020)

Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Bo Yang; Emmanuel S. Boss; Nils Haëntjens; Matthew C. Long; Michael J. Behrenfeld; Rachel Eveleth; Scott C. Doney (Frontiers in Marine Science, 2020)

Design of an Adhesive Film-Based Microfluidic Device for Alginate Hydrogel-Based Cell Encapsulation - Kevin Enck; Shiny Priya Rajan; Julio Aleman; Simone Castagno; Emily Long; Fatma Khalil; Adam R. Hall; Emmanuel C. Opara (Annals of Biomedical Engineering, 2020)

Chronic Kidney Disease Increases Cerebral Microbleeds in Mouse and Man - Wei Ling Lau; Ane C. F. Nunes; Vitaly Vasilevko; David Floriolli; Long Lertpanit; Javad Savoj; Maria Bangash; Zhihui Yao; Krunal Shah; Sameen Naqvi; Annlia Paganini-Hill; Nosratola D. Vaziri; et al. (Translational Stroke Research, 2020)

Ebullition of oxygen from seagrasses under supersaturated conditions - Matthew H. Long; Kevin Sutherland; Scott D. Wankel; David J. Burdige; Richard C. Zimmerman (Limnology and Oceanography, 2020)
Gas ebullition from aquatic systems to the atmosphere represents a potentially important fraction of primary production that goes unquantified by measurements of dissolved gas concentrations. Although gas ebullition from photosynthetic surfaces has often been observed, it is rarely quantified. The resulting underestimation of photosynthetic activity may significantly bias the determination of ecosystem trophic status and estimated rates of biogeochemical cycling from in situ measures of dissolved oxygen. Here, we quantified gas ebullition rates in Zostera marina meadows in Virginia, U.S.A. using simple funnel traps and analyzed the oxygen concentration and isotopic composition of the captured gas. Maximum hourly rates of oxygen ebullition (3.0 mmol oxygen m −2 h −1 ) were observed during the coincidence of high irradiance and low tides, particularly in the afternoon when oxygen and temperature maxima occurred. The daily ebullition fluxes (up to 11 mmol oxygen m −2 d −1 ) were roughly equivalent to net primary production rates determined from dissolved oxygen measurements indicating that bubble ebullition can represent a major component of primary production that is not commonly included in ecosystem‐scale estimates. Oxygen content comprised 20–40% of the captured bubble gas volume and correlated negatively with its δ 18 O values, consistent with a predominance of mixing between the higher δ 18 O of atmospheric oxygen in equilibrium with seawater and the lower δ 18 O of oxygen derived from photosynthesis. Thus, future studies interested in the metabolism of highly productive, shallow water ecosystems, and particularly those measuring in situ oxygen flux, should not ignore the bubble formation and ebullition processes described here.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Modernizing and expanding the NASA Space Geodesy Network to meet future geodetic requirements - S. M. Merkowitz; S. Bolotin; P. Elosegui; J. Esper; J. Gipson; L. Hilliard; E. Himwich; E. D. Hoffman; D. D. Lakins; R. C. Lamb; F. G. Lemoine; J. L. Long; et al. (Journal of Geodesy, 2019)

Study on arsenic removal in aqueous chloride solution with lead oxide - H. Long; Y. J. Zheng; Y. L. Peng; G. Z. Jin; W. H. Deng; S. C. Zhang (International Journal of Environmental Science and Technology, 2019)

Closing the oxygen mass balance in shallow coastal ecosystems - Matthew H. Long; Jennie E. Rheuban; Daniel C. McCorkle; David J. Burdige; Richard C. Zimmerman (Limnology and Oceanography, 2019)
The oxygen concentration in marine ecosystems is influenced by production and consumption in the water column and fluxes across both the atmosphere–water and benthic–water boundaries. Each of these fluxes has the potential to be significant in shallow ecosystems due to high fluxes and low water volumes. This study evaluated the contributions of these three fluxes to the oxygen budget in two contrasting ecosystems, a Zostera marina (eelgrass) meadow in Virginia, U.S.A., and a coral reef in Bermuda. Benthic oxygen fluxes were evaluated by eddy covariance. Water column oxygen production and consumption were measured using an automated water incubation system. Atmosphere–water oxygen fluxes were estimated by parameterizations based on wind speed or turbulent kinetic energy dissipation rates. We observed significant contributions of both benthic fluxes and water column processes to the oxygen mass balance, despite the often‐assumed dominance of the benthic communities. Water column rates accounted for 45% and 58% of the total oxygen rate, and benthic fluxes accounted for 23% and 39% of the total oxygen rate in the shallow (~ 1.5 m) eelgrass meadow and deeper (~ 7.5 m) reef site, respectively. Atmosphere–water fluxes were a minor component at the deeper reef site (3%) but a major component at the shallow eelgrass meadow (32%), driven by diel changes in the sign and strength of atmosphere–water gradient. When summed, the measured benthic, atmosphere–water, and water column rates predicted, with 85–90% confidence, the observed time rate of change of oxygen in the water column and provided an accurate, high temporal resolution closure of the oxygen mass balance.

Age, composition and tectonic implications of late Ordovician-early Silurian igneous rocks of the Loel Volcanic Belt, NW Laos - Yongzhen Long; Dexian Zhang; Dezhi Huang; Xiaoyong Yang; Shanshan Chen; Richard C. Bayless (International Geology Review, 2019)

Combining potassium chloride leaching with vertical electrokinetics to remediate cadmium-contaminated soils - Qiang Ma; Jun Li; Charles C. C. Lee; Xinxian Long; Yongmao Liu; Qi-Tang Wu (Environmental Geochemistry and Health, 2019)

A novel application of membrane distillation to facilitate nickel recovery from electroplating wastewater - Hung C. Duong; Thao M. Pham; Son T. Luong; Ky V. Nguyen; Diu T. Nguyen; Ashley J. Ansari; Long D. Nghiem (Environmental Science and Pollution Research, 2019)

Enormous gill chambers of deep‐sea coffinfishes (Lophiiformes: Chaunacidae) support unique ventilatory specialisations such as breath holding and extreme inflation - Nicholas P. Long; Stacy C. Farina (Journal of Fish Biology, 2019)
Deep sea habitats tend to favor species with low energetic demands, and therefore we predict that deep sea fishes will have behavioral and morphological specializations of the gill ventilatory system to reduce the energetic cost of pumping water across the gills. However, it is difficult to study functional morphology of deep sea fishes due the lack of ability to conduct laboratory experiments with living fishes. For this study, we combined analysis of publicly available video recorded by remote‐operated vehicles (ROV) with detailed anatomical study of museum specimens to document the functional morphology of the massive gill chambers that are observed in coffinfishes (Lophiiformes: Chaunacidae). Chaunacids, like other lophiiforms, exhibit highly specialised ventilatory anatomy such as an enlarged branchiostegal apparatus and restricted gill openings, but videos show them using this anatomy in a new and unusual way. We observed eight individuals ventilating extremely slowly at rates of 0.03–0.004 Hz, during which the gill chambers were full yet we saw no inhalation or exhalation for periods of 26 to 245 s. This holding breath behaviour has not been observed in any other fishes and is probably highly energetically efficient. This inflation of the gill chambers also increases body volume by up to 30%, making them more globose and difficult to be taken as prey, much like stomach inflation in pufferfishes (Tetraodontidae). We also used micro computed‐tomography (CT) scans to document the enormous branchiostegal rays and associated muscles that support this unique behaviour.

WebCAT: Piloting the Development of a Web Camera Coastal Observing Network for Diverse Applications - Gregory Dusek; Debra Hernandez; Mark Willis; Jenna A. Brown; Joseph W. Long; Dwayne E. Porter; Tiffany C. Vance (Frontiers in Marine Science, 2019)

The Frequency and Anatomical Characteristics of Anomalous Dark Rings in Black Cherry, and Their Relation to Cherry Scallop Shell Moth Defoliations - Robert P Long; Michael C Wiemann; Thomas A Kuster (Forest Science, 2019)

Genetic modification of western wheatgrass (Pascopyrum smithii) for the phytoremediation of RDX and TNT - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Planta, 2019)

Subdividing the Holocene Series/Epoch: formalization of stages/ages and subseries/subepochs, and designation of GSSPs and auxiliary stratotypes - MIKE WALKER; Martin J. Head; John Lowe; Max Berkelhammer; Svante BjÖrck; Hai Cheng; Les C. Cwynar; David Fisher; Vasileios Gkinis; Antony Long; Rewi Newnham; Sune Olander Rasmussen; et al. (Journal of Quaternary Science, 2019)
The Holocene, which currently spans ~11 700 years, is the shortest series/epoch within the geological time scale (GTS), yet it contains a rich archive of evidence in stratigraphical contexts that are frequently continuous and often preserved at high levels of resolution. On 14 June 2018, the Executive Committee of the International Union of Geological Sciences formally ratified a proposal to subdivide the Holocene into three stages/ages, along with their equivalent subseries/subepochs, each anchored by a Global boundary Stratotype Section and Point (GSSP). The new stages are the Greenlandian (Lower/Early Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP2 ice core and dated at 11 700 a b2k (before 2000 CE); the Northgrippian (Middle Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP1 ice core and dated at 8236 a b2k; and the Meghalayan (Upper/Late Holocene Subseries/Subepoch) with its GSSP in a speleothem from Mawmluh Cave, north‐eastern India, with a date of 4250 a b2k. We explain the nomenclature of the new divisions, describe the procedures involved in the ratification process, designate auxiliary stratotypes to support the GSSPs and consider the implications of the subdivision for defining the Anthropocene as a new unit within the GTS.

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Impact of Dairy Manure Processing Using Polyacrylamide on Antibiotic-Resistant Bacterial Level - Sunghwa Han; Sharon C. Long; Troy Runge; Cuihua Dong; Zong Liu (Water, Air, & Soil Pollution, 2019)

Reduced body size of insular black-tailed deer is caused by slowed development - Eric S. Long; Karissa L. Courtney; Julia C. Lippert; Cara M. Wall-Scheffler (Oecologia, 2019)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Potential impacts of climate change on storage conditions for commercial agriculture: an example for potato production in Michigan - Julie A. Winkler; Logan Soldo; Ying Tang; Todd Forbush; David S. Douches; Chris M. Long; Courtney P. Leisner; C. Robin Buell (Climatic Change, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Effects of Level, Loading Rate, Injury and Repair on Biomechanical Response of Ovine Cervical Intervertebral Discs - Rose G. Long; Ivan Zderic; Boyko Gueorguiev; Stephen J. Ferguson; Mauro Alini; Sibylle Grad; James C. Iatridis (Annals of Biomedical Engineering, 2018)

Lightning-induced beads, ‘fulguroids’, associated with kimberlite eruptions in the Kalahari, Botswana - M. J. McFarlane; C. W. Long; S. H. Coetzee (International Journal of Earth Sciences, 2018)

Dynamic modeling of barrier island response to hurricane storm surge under future sea level rise - Davina L. Passeri; Matthew V. Bilskie; Nathaniel G. Plant; Joseph W. Long; Scott C. Hagen (Climatic Change, 2018)

Multiple non-catalytic ADAMs are novel integrin α4 ligands - Lei Wang; Jason A. Hoggard; Erica D. Korleski; Gideon V. Long; Brandy C. Ree; Kenneth Hensley; Stephen R. Bond; Tyra G. Wolfsberg; JianMing Chen; Tonya N. Zeczycki; Lance C. Bridges (Molecular and Cellular Biochemistry, 2018)

Evaluation of ageing accuracy with complementary non‐lethal methods for slow‐growing, northern populations of shoal bass - J. M. Long; C. T. Holley; A. T. Taylor (Fisheries Management and Ecology, 2018)
In the upper Chattahoochee River basin, where some populations of shoal bass, Micropterus cataractae Williams & Burgess, are imperilled, age and growth data are lacking. Age and growth of shoal bass in this basin were assessed with non‐lethal means using scales and mark–recapture. Mark–recapture data allowed for estimation of accuracy and determination of effects of any scale‐based inaccuracies on growth models. Scale‐based age estimates were accurate for 57% of the samples, and errors of 1 to 3 years included equal numbers of over‐ and underestimates of age. von Bertalanffy growth models based on scale ages were similar to those based on mark–recapture ages for ages 3–8 but noticeably divergent for younger and older fish. Scales provided estimates of longevity up to 12 years of age, and growth models produced from mark–recapture suggest scale ages underestimated age, especially for older fish. These populations of shoal bass live longer and grow slower than other populations, suggesting regional management strategies may be needed.

The wildlife snaring crisis: an insidious and pervasive threat to biodiversity in Southeast Asia - Thomas N. E. Gray; Alice C. Hughes; William F. Laurance; Barney Long; Anthony J. Lynam; Hannah O’Kelly; William J. Ripple; Teak Seng; Lorraine Scotson; Nicholas M. Wilkinson (Biodiversity and Conservation, 2018)

Reveille Russet: An Early, Widely Adapted, High-Count-Carton Russet for the Fresh Market - J. C. Miller; D. C. Scheuring; J. W. Koym; D. G. Holm; J. J. Pavek; R. G. Novy; J. L. Whitworth; J. C. Stark; B. A. Charlton; S. Yilma; N. R. Knowles; M. J. Pavek; et al. (American Journal of Potato Research, 2018)

Specific effects of prenatal DEHP exposure on neuroendocrine gene expression in the developing hypothalamus of male rats - Na Gao; Ruixia Hu; Yujing Huang; Long Dao; Caifeng Zhang; Yongzhe Liu; Lina Wu; Xutong Wang; Weiling Yin; Andrea C. Gore; Zengrong Sun (Archives of Toxicology, 2018)

Density‐mediated indirect effects from active predators and narrow habitat domain prey - S. A. Rinehart; S. C. Schroeter; J. D. Long (Ecology, 2017)
The hunting‐mode–habitat‐domain‐range framework suggests that the mechanism driving trophic cascades (i.e., trait‐mediated indirect interactions [ TMII s] vs. density‐mediated indirect interactions [ DMII s]) should depend upon the functional traits of predators and prey. For example, trophic cascades containing active, broad habitat domain range ( BHDR ) predators interacting with narrow habitat domain range ( NHDR ) prey are predicted to arise primarily via TMII s, because these prey should reduce their conspicuous activity in the presence of these predators. Unfortunately, this hypothesis is difficult to test given the strong bias against studies assessing trophic cascades containing NHDR prey. Furthermore, this hypothesis ignores evidence that (1) active predators can have high consumption rates on prey, (2) continuously responding to active predators foraging across broad areas is energetically costly for prey, and (3) cues from active, BHDR predators may not influence prey density. We examined the TMII s and total indirect interaction ( TII ) produced during interactions between an active, BHDR ladybeetle predator ( Naemia seriata ) and its NHDR prey (scale insects). We exposed scale insects to nonlethal and lethal ladybeetle predators in laboratory mesocosms for 15 weeks. We measured the growth of the scale insect's host plant (cordgrass) and the population density of scale insects. Contrary to theory, nonlethal ladybeetles did not induce TMII s. However, lethal ladybeetles increased cordgrass total and root dry biomass by 36% and 44%, respectively, suggesting the presence of strong DMII s. Additionally, both lethal and nonlethal ladybeetles reduced scale insect population density. Our findings suggest that DMII s, rather than TMII s, can result from interactions between active BHDR predators and NHDR prey.

Phytodetoxification of TNT by transplastomic tobacco (Nicotiana tabacum) expressing a bacterial nitroreductase - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Plant Molecular Biology, 2017)

A framework for assessing readiness for tiger Panthera tigris reintroduction: a case study from eastern Cambodia - T. N. E. Gray; R. Crouthers; K. Ramesh; J. Vattakaven; J. Borah; M. K. S. Pasha; T. Lim; C. Phan; R. Singh; B. Long; S. Chapman; O. Keo; et al. (Biodiversity and Conservation, 2017)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Reconstruction of Indian monsoon precipitation variability between 4.0 and 1.6 ka BP using speleothem δ18O records from the Central Lesser Himalaya, India - Lalit M. Joshi; Bahadur Singh Kotlia; S. M. Ahmad; C.-C. Wu; Jaishri Sanwal; Waseem Raza; Anoop K. Singh; C.-C. Shen; Tengwen Long; Arun K. Sharma (Arabian Journal of Geosciences, 2017)

Erratum to: Temporal trends of lipophilic persistent organic pollutants in serum from Danish nulliparous pregnant women 2011–2013 - Christian Bjerregaard-Olesen; Manhai Long; Mandana Ghisari; Bodil H. Bech; Ellen A. Nohr; Niels Uldbjerg; Tine B. Henriksen; Jørn Olsen; Eva C. Bonefeld-Jørgensen (Environmental Science and Pollution Research, 2017)

Temporal trends of lipophilic persistent organic pollutants in serum from Danish nulliparous pregnant women 2011–2013 - Christian Bjerregaard-Olesen; Manhai Long; Mandana Ghisari; Bodil H Bech; Ellen A Nohr; Niels Uldbjerg; Tine B Henriksen; Jørn Olsen; Eva C Bonefeld-Jørgensen (Environmental Science and Pollution Research, 2017)

Molecular variation and population structure in critically endangered Turks and Caicos Rock Iguanas: identifying intraspecific conservation units and revising subspecific taxonomy - Mark E. Welch; Giuliano Colosimo; Stesha A. Pasachnik; Catherine L. Malone; Jace Hilton; June Long; Angela H. Getz; Allison C. Alberts; Glenn P. Gerber (Conservation Genetics, 2017)

Infectious bursal disease virus as a replication-incompetent viral vector expressing green fluorescent protein - Yung-Yi C. Mosley; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2017)

Processes driving seasonal variability in DMS, DMSP, and DMSO concentrations and turnover in coastal Antarctic waters - E. C. Asher; J. W. H. Dacey; M. Stukel; M. C. Long; P. D. Tortell (Limnology and Oceanography, 2017)
This study presents new measurements of the concentrations and turnover rates of dimethyl sulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethyl sulfoxide (DMSO) in coastal waters near Palmer Station, Antarctica, during the spring and summer of 2012–2013. Using several novel analytical and experimental techniques, we document variability in DMS, DMSP, and DMSO (DMS/P/O) concentrations and quantify dominant production and removal terms in the mixed layer DMS budget. Our results demonstrate considerable seasonal variability in the concentration of DMS (range 0–20 nM), total DMSP (8–160 nM), and total DMSO (4–160 nM). Over the seasonal cycle, dissolved DMSP concentrations were well correlated with total DMSP concentrations and the abundance of Phaeocystis antarctica , while DMSO concentrations (total and dissolved) were well correlated with DMS concentrations. DMSP cleavage from the dissolved pool (mean rate = 5.5 nM d −1 ) and release from microzooplankton grazing (mean 5.6 nM d −1 ) were the dominant sources of DMS, with smaller DMS production rates associated with DMSO reduction from the dissolved pool (mean 2.6 nM d −1 ) and krill grazing (mean 0.82 nM d −1 ). Specific rate constants for DMSP cleavage were inversely related to net primary production. Bacterial uptake was a primary contributor to DMS removal (mean −12 nM d −1 ), and we observed a significant correlation between bacterial production and gross DMS loss rate constants. Estimated sea‐air flux and photo‐oxidation constituted secondary DMS sinks. Our experimental and analytical methods provide insight into the DMS/P/O cycle at Palmer Station, and a starting point for future studies examining inter‐annual DMS/P/O variability in coastal Antarctic waters.

Optimum breeding strategies using genomic selection for hybrid breeding in wheat, maize, rye, barley, rice and triticale - Jose J. Marulanda; Xuefei Mi; Albrecht E. Melchinger; Jian-Long Xu; T. Würschum; C. Friedrich H. Longin (Theoretical and Applied Genetics, 2016)

Implication of subsurface flow on rainfall-induced landslide: a case study - Wei Chao Li; F. C. Dai; Ying Qi Wei; Ming Long Wang; Hong Min; Lee Min Lee (Landslides, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Development of Dryland Oilseed Production Systems in Northwestern Region of the USA - D. S. Long; F. L. Young; W. F. Schillinger; C. L. Reardon; J. D. Williams; B. L. Allen; W. L. Pan; D. J. Wysocki (BioEnergy Research, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Groundwater Molybdenum from Emerging Industries in Taiwan - Kuo-Sheng Tsai; Yu-Min Chang; Jimmy C. M. Kao; Kae-Long Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Microbial diversity on intravascular catheters from paediatric patients - L. Zhang; N. Marsh; D. Long; M. Wei; M. Morrison; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

QTL identification on two genetic systems for rapeseed glucosinolate and erucic acid contents over two seasons - J. F. Xu; Y. Long; J. G. Wu; H. M. Xu; Z. G. Zhao; J. Wen; J. L. Meng; C. H. Shi (Euphytica, 2015)

Timing and conditions of metamorphism and melt crystallization in Greater Himalayan rocks, eastern and central Bhutan: insight from U–Pb zircon and monazite geochronology and trace-element analyses - K. Zeiger; S. M. Gordon; S. P. Long; A. R. C. Kylander-Clark; K. Agustsson; M. Penfold (Contributions to Mineralogy and Petrology, 2015)

Pl 17 is a novel gene independent of known downy mildew resistance genes in the cultivated sunflower (Helianthus annuus L.) - L. L. Qi; Y. M. Long; C. C. Jan; G. J. Ma; T. J. Gulya (Theoretical and Applied Genetics, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Genome edited sheep and cattle - Chris Proudfoot; Daniel F. Carlson; Rachel Huddart; Charles R. Long; Jane H. Pryor; Tim J. King; Simon G. Lillico; Alan J. Mileham; David G. McLaren; C. Bruce A. Whitelaw; Scott C. Fahrenkrug (Transgenic Research, 2015)

Editorial: Quaternary revolutions - DAN J. CHARMAN; GEOFF A. T. DULLER; ANTONY J. LONG; DANIELLE C. SCHREVE; JAMES D. SCOURSE (Journal of Quaternary Science, 2015)

Satellite radar anisotropy observed in urban areas - Aaron C. Paget; Steve Frolking; David G. Long; Tom Milliman (International Journal of Remote Sensing, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Environmental fate and exposure; neonicotinoids and fipronil - J.-M. Bonmatin; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; E. Long; M. Marzaro; E. A. D. Mitchell; D. A. Noome; N. Simon-Delso; et al. (Environmental Science and Pollution Research, 2015)

Soil Nailing in Dublin Boulder Clay - C. O. Menkiti; M. Long; G. W. E. Milligan; P. Higgins (Geotechnical and Geological Engineering, 2014)

Breast cancer risk after exposure to perfluorinated compounds in Danish women: a case–control study nested in the Danish National Birth Cohort - Eva C. Bonefeld-Jørgensen; Manhai Long; Stine Overvad Fredslund; Rossana Bossi; Jørn Olsen (Cancer Causes & Control, 2014)

A phylogeny of softshell turtles (Testudines: Trionychidae) with reference to the taxonomic status of the critically endangered, giant softshell turtle, Rafetus swinhoei - Minh Le; Ha T. Duong; Long D. Dinh; Truong Q. Nguyen; Peter C. H. Pritchard; Timothy McCormack (Organisms Diversity & Evolution, 2014)

An influenza A virus hemagglutinin (HA) epitope inserted in and expressed from several loci of the infectious bursal disease virus genome induces HA-specific antibodies - Yung-Yi C. Mosley; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Temperature impacts on anaerobic biotransformation of LNAPL and concurrent shifts in microbial community structure - Natalie R. Zeman; Maria Irianni Renno; Mitchell R. Olson; L. Paige Wilson; Thomas C. Sale; Susan K. De Long (Biodegradation, 2014)

Direct production of bioethanol from Jerusalem artichoke inulin by gene-engineering Saccharomyces cerevisiae 6525 with exoinulinase gene - L. Wang; Y. C. Du; X. F. Meng; X. H. Long; Z. P. Liu; H. Shao (Plant Biosystems, 2014)

Optimizing medium for producing ethanol from industrial crop Jerusalem artichoke by one-step fermentation and recombinant Saccharomyces cerevisiae - Y. C. Du; X. H. Long; Z. P. Liu; H. B. Shao (Plant Biosystems, 2014)

Exogenous CaCl 2 promoted the indole alkaloid accumulation in seedlings of Catharanthus roseus under NaCl stress - L. Liu; J. Y. Wang; F. Chen; C. Liu; X. H. Long; Z. P. Liu; H. B. Shao (Plant Biosystems, 2014)

Phylogeographic patterns of the Aconitum nemorum species group (Ranunculaceae) shaped by geological and climatic events in the Tianshan Mountains and their surroundings - Xiao-Long Jiang; Ming-Li Zhang; Hong-Xiang Zhang; Stewart C. Sanderson (Plant Systematics and Evolution, 2014)

Differential gene expression in human hepatocyte cell lines exposed to the antiretroviral agent zidovudine - Jia-Long Fang; Tao Han; Qiangen Wu; Frederick A. Beland; Ching-Wei Chang; Lei Guo; James C. Fuscoe (Archives of Toxicology, 2013)

Association mapping of salt tolerance in barley (Hordeum vulgare L.) - Nguyen Viet Long; Oene Dolstra; Marcos Malosetti; Benjamin Kilian; Andreas Graner; Richard G. F. Visser; C. Gerard van der Linden (Theoretical and Applied Genetics, 2013)

2-epi-5-epi-Valiolone synthase activity is essential for maintaining phycobilisome composition in the cyanobacterium Anabaena variabilis ATCC 29413 when grown in the presence of a carbon source - Edward Spence; Samantha J. Bryan; Mohamed Lisfi; John Cullum; Walter C. Dunlap; J. Malcolm Shick; Conrad W. Mullineaux; Paul F. Long (Photosynthesis Research, 2013)

GSTM1 and GSTT1 genetic polymorphisms and risk of anti-tuberculosis drug-induced hepatotoxicity: an updated meta-analysis - C. Li; J. Long; X. Hu; Y. Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Erratum to: Demography and movement patterns of leopard sharks (Triakis semifasciata ) aggregating near the head of a submarine canyon along the open coast of southern California, USA - A. P. Nosal; D. C. Cartamil; J. W. Long; M. Lührmann; N. C. Wegner; J. B. Graham (Environmental Biology of Fishes, 2013)

Demography and movement patterns of leopard sharks (Triakis semifasciata) aggregating near the head of a submarine canyon along the open coast of southern California, USA - A. P. Nosal; D. C. Cartamil; J. W. Long; M. Lührmann; N. C. Wegner; J. B. Graham (Environmental Biology of Fishes, 2013)

Irreversible Electroporation: An In Vivo Study with Dorsal Skin Fold Chamber - Zhenpeng Qin; Jing Jiang; Gary Long; Bruce Lindgren; John C. Bischof (Annals of Biomedical Engineering, 2013)

Remediation of an electroplating contaminated soil by EDTA flushing: chromium release and soil dissolution - Weihua Zhang; Daniel C. W. Tsang; Hao Chen; Long Huang (Journal of Soils and Sediments, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Formal subdivision of the Holocene Series/Epoch: a Discussion Paper by a Working Group of INTIMATE (Integration of ice‐core, marine and terrestrial records) and the Subcommission on Quaternary Stratigraphy (International Commission on Stratigraphy) - M. J. C. Walker; M. Berkelhammer; S. Björck; L. C. Cwynar; D. A. Fisher; A. J. Long; J. J. Lowe; R. M. Newnham; S. O. Rasmussen; H. Weiss (Journal of Quaternary Science, 2012)
This discussion paper, by a Working Group of INTIMATE (Integration of ice‐core, marine and terrestrial records) and the Subcommision on Quaternary Stratigraphy (SQS) of the International Commission on Stratigraphy (ICS), considers the prospects for a formal subdivision of the Holocene Series/Epoch. Although previous attempts to subdivide the Holocene have proved inconclusive, recent developments in Quaternary stratigraphy, notably the definition of the Pleistocene–Holocene boundary and the emergence of formal subdivisions of the Pleistocene Series/Epoch, mean that it may be timely to revisit this matter. The Quaternary literature reveals a widespread but variable informal usage of a tripartite division of the Holocene (‘early’, ‘middle’ or ‘mid’, and ‘late’), and we argue that this de facto subdivision should now be formalized to ensure consistency in stratigraphic terminology. We propose an Early–Middle Holocene Boundary at 8200 a BP and a Middle–Late Holocene Boundary at 4200 a BP, each of which is linked to a Global Stratotype Section and Point (GSSP). Should the proposal find a broad measure of support from the Quaternary community, a submission will be made to the International Union of Geological Sciences (IUGS), via the SQS and the ICS, for formal ratification of this subdivision of the Holocene Series/Epoch. Copyright © 2012 John Wiley & Sons, Ltd.

Design Optimization of Liquid-Phase Flow Patterns for Microfabricated Lung on a Chip - C. Long; C. Finch; M. Esch; W. Anderson; M. Shuler; J. Hickman (Annals of Biomedical Engineering, 2012)

The cell adhesion gene PVRL3 is associated with congenital ocular defects - Salil A. Lachke; Anne W. Higgins; Maiko Inagaki; Irfan Saadi; Qiongchao Xi; Michelle Long; Bradley J. Quade; Michael E. Talkowski; James F. Gusella; Atsuko Fujimoto; Michael L. Robinson; Ying Yang; et al. (Human Genetics, 2012)

Cannabidiol potentiates Δ9-tetrahydrocannabinol (THC) behavioural effects and alters THC pharmacokinetics during acute and chronic treatment in adolescent rats - Charlotte Klein; Emily Karanges; Adena Spiro; Alexander Wong; Jarrah Spencer; Thanh Huynh; Nathan Gunasekaran; Tim Karl; Leonora E. Long; Xu-Feng Huang; Kelly Liu; Jonathon C. Arnold; et al. (Psychopharmacology, 2011)

Corrigendum: Late Devensian and Holocene relative sea‐level change in North Wales, UK - M. J. Roberts; J. D. Scourse; J. D. Bennell; D. G. Huws; C. F. Jago; B. T. Long (Journal of Quaternary Science, 2011)

Sequence polymorphism and expression analysis of genes encoding gibberellin 20-oxidase from Dasypyrus villosum - P. Cai; H. Long; J. Liang; C. Wang; G. Deng; Z. Pan; Z. Peng; M. Yu (Cereal Research Communications, 2011)

Influence of rocky slope gradient on root anchorage of Vitex negundo L. - F. Long; H.-L. Sun; S.-C. Li (Plant Biosystems, 2011)

Insect attraction to wind turbines: does colour play a role? - C. V. Long; J. A. Flint; P. A. Lepper (European Journal of Wildlife Research, 2011)

Late Devensian and Holocene relative sea‐level change in North Wales, UK - M. J. Roberts; J. D. Scourse; J. D. Bennell; D. G. Huws; C. F. Jago; B. T. Long (Journal of Quaternary Science, 2011)
Deglacial sea‐level index points defining relative sea‐level (RSL) change are critical for testing glacial isostatic adjustment (GIA) model output. Only a few observations are available from North Wales and until recently these provided a poor fit to GIA model output for the British‐Irish Ice Sheet. We present results of an integrated offshore geophysical (seismic reflection), coring (drilling rig), sedimentological, micropalaeontological (foraminifera), biostratigraphical (palynology) and geochronological (AMS 14 C) investigation into a sequence of multiple peat/organic sediment horizons interbedded within a thick estuarine–marine sequence of minerogenic clay‐silts to silty sands from the NE Menai Strait, North Wales. Ten new sea‐level index points and nine new limiting dates from the Devensian Late‐glacial and early Holocene are integrated with twelve pre‐existing Holocene sea‐level index points and one limiting point from North Wales to generate a regional RSL record. This record is similar to the most recent GIA predictions for North Wales RSL change, supporting either greater ice load and later deglaciation than in the GIA predictions generated before 2004, or a modified eustatic function. There is no evidence for a mid‐Holocene highstand. Tidally corrected RSL data indicate initial breaching of the Menai Strait between 8.8 and 8.4 ka BP to form a tidal causeway, with final submergence between 5.8 and 4.6 ka BP. Final breaching converted the NE Menai Strait from a flood‐dominated estuary into a high energy ebb tidal delta with extensive tidal scouring of pre‐existing Late‐glacial and Holocene sequences. The study confirms the value of utilising offshore drilling/coring technology to recover sea‐level records which relate to intervals when rates of both eustatic and isostatic change were at their greatest, and therefore of most value for constraining GIA models. Copyright © 2011 John Wiley & Sons, Ltd.

Residual social, memory and oxytocin-related changes in rats following repeated exposure to γ-hydroxybutyrate (GHB), 3,4-methylenedioxymethamphetamine (MDMA) or their combination - Petra S. van Nieuwenhuijzen; Leonora E. Long; Glenn E. Hunt; Jonathon C. Arnold; Iain S. McGregor (Psychopharmacology, 2010)

KISS1 over-expression suppresses metastasis of pancreatic adenocarcinoma in a xenograft mouse model - Lacey R. McNally; Danny R. Welch; Benjamin H. Beck; Lewis J. Stafford; Joshua W. Long; Jeffery C. Sellers; Zhi Q. Huang; William E. Grizzle; Cecil R. Stockard; Kevin T. Nash; Donald J. Buchsbaum (Clinical & Experimental Metastasis, 2010)

A follow-up study: acute behavioural effects of Δ9-THC in female heterozygous Neuregulin 1 transmembrane domain mutant mice - Leonora E. Long; Rose Chesworth; Jonathon C. Arnold; Tim Karl (Psychopharmacology, 2010)

Quantitative trait locus analysis identifies Gabra3 as a regulator of behavioral despair in mice - Brooke H. Miller; Laura E. Schultz; Bradley C. Long; Mathew T. Pletcher (Mammalian Genome, 2010)

Extrapulmonary tissue responses in cynomolgus macaques (Macaca fascicularis) infected with highly pathogenic avian influenza A (H5N1) virus - A.-E. Tolnay; C. R. Baskin; T. M. Tumpey; P. J. Sabourin; C. L. Sabourin; J. P. Long; J. A. Pyles; R. A. Albrecht; A. García-Sastre; M. G. Katze; H. Bielefeldt-Ohmann (Archives of Virology, 2010)

Species richness and abundance of native leaf miners are affected by the presence of the invasive horse-chestnut leaf miner - Christelle Péré; Sylvie Augustin; Rumen Tomov; Long-hui Peng; Ted C. J. Turlings; Marc Kenis (Biological Invasions, 2010)

Biochemical and hormonal changes during acute fasting and re-feeding in bottlenose dolphins ( Tursiops truncatus ) - Rudy M. Ortiz; Brett Long; Dave Casper; C. Leo Ortiz; Terrie M. Williams (Marine Mammal Science, 2010)

Missaukee: A Round White Potato Variety Combining Chip-Processing With Resistance to Late Blight, Verticillium Wilt and Golden Cyst Nematode - David S. Douches; J. Coombs; K. Felcher; W. W. Kirk; C. Long; G. Bird (American Journal of Potato Research, 2010)

Kalkaska: A Round White Chip-Processing Potato Variety with Common Scab Resistance - D. S. Douches; J. Coombs; R. Hammerschmidt; W. W. Kirk; C. Long (American Journal of Potato Research, 2009)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

Measurements and products from the Solar Backscatter Ultraviolet (SBUV/2) and Ozone Mapping and Profiler Suite (OMPS) instruments - L. E. Flynn; D. McNamara; C. T. Beck; I. Petropavlovskikh; E. Beach; Y. Pachepsky; Y. P. Li; M. Deland; L. -K. Huang; C. S. Long; R. Tiruchirapalli; S. Taylor (International Journal of Remote Sensing, 2009)

Modulation of natural variability on a trend analysis of the updated cohesive SBUV(/2) total ozone - Shi-King Yang; C. S. Long; A. J. Miller; Xuming He; Yunwen Yang; D. J. Wuebbles; George Tiao (International Journal of Remote Sensing, 2009)

Linking invasions and biogeography: Isolation differentially affects exotic and native plant diversity - Jeremy D. Long; Geoffrey C. Trussell; Ted Elliman (Ecology, 2009)
The role of native species diversity in providing biotic resistance to invasion remains controversial, with evidence supporting both negative and positive relationships that are often scale dependent. Across larger spatial scales, positive relationships suggest that exotic and native species respond similarly to factors other than diversity. In the case of island habitats, such factors may include island size and isolation from the mainland. However, previous island studies exploring this issue examined only a few islands or islands separated by extreme distances. In this study, we surveyed exotic and native plant diversity on 25 islands separated by

The role of organic acid exudates in liberating phosphorus from seagrass‐vegetated carbonate sediments - Matthew H. Long; Karen J. McGlathery; Joseph C. Zieman; Peter Berg (Limnology and Oceanography, 2008)
Sediment‐bound phosphorus (P) is a potential nutrient source for P‐limited seagrasses inhabiting carbonate sediments. We explored the role of organic acid (OA) exudation by seagrasses in liberating mineral P from carbonate sediments. Organic acids can act to increase available P by dissolving carbonate sediment, competing with P for binding sites and complexing dissolution end products, and also by fueling microbial processes that change pore‐water pH. We used dialysis tubing placed around individual roots in situ to quantify dissolved species immediately adjacent to roots (root zone) and compared these to bulk pore‐water concentrations in vegetated and nonvegetated sediments. Total OA concentrations were highest in the root zone (29.8 ± 1.8 [mol L −1 ) compared to bulk measures of 15.5 ± 1.9 and 7.5 ± 0.6 [mol L −1 in vegetated and nonvegetated sediments, respectively. Phosphate concentrations were also highest in the root zone and were linearly related to OA concentrations ( R 2 = 0.63). Organic acid concentrations increased along a seagrass productivity gradient, and ratios of OA concentrations to productivity showed a significant response to a gradient in P‐limitation of seagrasses. Organic acid concentrations found in and around roots, compared to those found in bulk sediment measures, indicate that seagrasses are a significant source of OA. Sampling at small spatial scales (mm) immediately adjacent to the roots is critical, because bulk sediment pore‐water measures did not capture the observed fluctuations caused by the rapid reaction and consumption of OA in the sediment. Root‐zone processes can liberate considerable quantities of P, and OA exudates likely contribute significantly to the success of T. testudinum in P‐limited environments.

Ranging of Rhinopithecus bieti in the Samage Forest, China. II. Use of Land Cover Types and Altitudes - Dayong Li; Cyril C. Grueter; Baoping Ren; Yongcheng Long; Ming Li; Zhengsong Peng; Fuwen Wei (International Journal of Primatology, 2008)

Ranging of Rhinopithecus bieti in the Samage Forest, China. I. Characteristics of Range Use - Cyril C. Grueter; Dayong Li; Carel P. van Schaik; Baoping Ren; Yongcheng Long; Fuwen Wei (International Journal of Primatology, 2008)

Measuring Daily Ranging Distances of Rhinopithecus bieti via a Global Positioning System Collar at Jinsichang, China: A Methodological Consideration - Baoping Ren; Ming Li; Yongcheng Long; Cyril C. Grüter; Fuwen Wei (International Journal of Primatology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Performance of Anaerobic Process on Toxicity Reduction During Treating Printing and Dyeing Wastewater - J. Wang; Z.-J. Zhang; L.-N. Chi; X.-L. Qiao; H.-X. Zhu; M.-C. Long; Z.-F. Zhang (Bulletin of Environmental Contamination and Toxicology, 2007)

TOPO TA is A‐OK: a test of phylogenetic bias in fungal environmental clone library construction - D. Lee Taylor; Ian C. Herriott; James Long; Keith O'Neill (Environmental Microbiology, 2007)
Summary TA cloning methods are widely used in analyses of environmental microbial diversity, yet the potential of TA methods to yield phylogenetically biased results has received little attention. To test for a TA bias, we constructed clone libraries of fungal amplicons spanning the ribosomal internally transcribed spacer (ITS) and partial large subunit (LSU) from 92 boreal forest soil DNA extracts using two contrasting methods: the Invitrogen TOPO‐TA system and the Lucigen PCR‐SMART system. The Lucigen system utilizes blunt‐ended rather than TA cloning and transcription terminators to reduce biases due to toxicity of expressed inserts. We analysed 588 clone sequences from the two libraries. Species diversity estimators applied to operational taxonomical units (OTUs) were slightly higher for Invitrogen than Lucigen, but confidence intervals for accumulation curves overlapped. Abundances of OTUs were correlated between the libraries ( r 2 = 0.5, P

A comparative linkage map of oilseed rape and its use for QTL analysis of seed oil and erucic acid content - D. Qiu; C. Morgan; J. Shi; Y. Long; J. Liu; R. Li; X. Zhuang; Y. Wang; X. Tan; E. Dietrich; T. Weihmann; C. Everett; et al. (Theoretical and Applied Genetics, 2006)

Relationships Between Toxicity and Concentrations of Chemical Contaminants in Sediments from Sydney Harbour, Australia, and Vicinity - S. McCready; G. F. Birch; E. R. Long; G. Spyrakis; C. R. Greely (Environmental Monitoring and Assessment, 2006)

Goodbye or welcome Gondwana? – insights into the phylogenetic biogeography of the leafy liverwort Plagiochila with a description of Proskauera, gen. nov. (Plagiochilaceae, Jungermanniales) - J. Heinrichs; M. Lindner; H. Groth; J. Hentschel; K. Feldberg; C. Renker; J. J. Engel; M. von Konrat; D. G. Long; H. Schneider (Plant Systematics and Evolution, 2006)

Beacon Chipper: A round white chip-processing potato variety - D. S. Douches; J. Coombs; R. Hammerschmidt; W. W. Kirk; C. Long; S. Snapp; Ben Kudwa; Don Flannery; Terry Bourgoin (American Journal of Potato Research, 2006)

An Evaluation of Australian Sediment Quality Guidelines - S. McCready; G. F. Birch; E. R. Long; G. Spyrakis; C. R. Greely (Archives of Environmental Contamination and Toxicology, 2006)

Microbial Community Responses to Atmospheric Carbon Dioxide Enrichment in a Warm-Temperate Forest - Adrien C. Finzi; Robert L. Sinsabaugh; Tammy M. Long; Marcy P. Osgood (Ecosystems, 2006)

Monitoring the Sensible Heat Flux over Urban Areas using Large Aperture Scintillometry: Case Study of Marseille City During the Escompte Experiment - J. -P. Lagouarde; M. Irvine; J. -M. Bonnefond; C. S. B. Grimmond; N. Long; T. R. Oke; J. A. Salmond; B. Offerle (Boundary-Layer Meteorology, 2006)

Cell architecture during gametophytic and embryogenic microspore development in Brassica napus L. - Gyanesh K. Satpute; Hong Long; José M. Seguí-Simarro; María C. Risueño; Pilar S. Testillano (Acta Physiologiae Plantarum, 2005)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Sex differential in methylation patterns of selected genes in Singapore Chinese - Barbara Sarter; Tiffany I. Long; Wan H. Tsong; Woon-Puay Koh; Mimi C. Yu; Peter W. Laird (Human Genetics, 2005)

The urban boundary-layer field campaign in marseille (ubl/clu-escompte): set-up and first results - P. G. Mestayer; P. Durand; P. Augustin; S. Bastin; J. -M. Bonnefond; B. Bnech; B. Campistron; A. Coppalle; H. Delbarre; B. Dousset; P. Drobinski; A. Druilhet; et al. (Boundary-Layer Meteorology, 2005)

Rapid non-genomic inhibitory effects of glucocorticoids on human neutrophil degranulation - L. Liu; Y. X. Wang; J. Zhou; F. Long; H. W. Sun; Y. Liu; Y. Z. Chen; C. L. Jiang (Inflammation Research, 2005)

Erratum - S. McCready; G. Spyrakis; C. R. Greely; G. F. Birch; E. R. Long (Environmental Monitoring and Assessment, 2005)

Polyamines and their biosynthetic enzymes during somatic embryo development in red spruce (Picea rubens Sarg.) - Rakesh Minocha; Subhash C. Minocha; Stephanie Long (In Vitro Cellular & Developmental Biology - Plant, 2004)

Conformational changes in actin–myosin isoforms probed by Ni(II)·Gly–Gly–His reactivity - Juliette Van Dijk; Chrystel Lafont; Menno L. W. Knetsch; Jean Derancourt; Dietmar J Manstein; Eric C. Long; Patrick Chaussepied (Journal of Muscle Research and Cell Motility, 2004)

Toxicity of Surficial Sediments from Sydney Harbour and Vicinity, Australia - S. McCready; G. Spyrakis; C. R. Greely; G. F. Birch; E. R. Long (Environmental Monitoring and Assessment, 2004)

Penicillium persicinum, a new griseofulvin, chrysogine and roquefortine C producing species from Qinghai province, China - Long Wang; Han-Bai Zhou; Jens C. Frisvad; Robert A. Samson (Antonie van Leeuwenhoek, 2004)

Will photosynthesis of maize ( Zea mays ) in the US Corn Belt increase in future [CO 2 ] rich atmospheres? An analysis of diurnal courses of CO 2 uptake under free‐air concentration enrichment (FACE) - A. D. B. Leakey; C. J. Bernacchi; F. G. Dohleman; D. R. Ort; S. P. Long (Global Change Biology, 2004)
The C 4 grass Zea mays (maize or corn) is the third most important food crop globally in terms of production and demand is predicted to increase 45% from 1997 to 2020. However, the effects of rising [CO 2 ] upon C 4 plants, and Z. mays specifically, are not sufficiently understood to allow accurate predictions of future crop production. A rainfed, field experiment utilizing free‐air concentration enrichment (FACE) technology in the primary area of global corn production (US Corn Belt) was undertaken to determine the effects of elevated [CO 2 ] on corn. FACE technology allows experimental treatments to be imposed upon a complete soil–plant–atmosphere continuum with none of the effects of experimental enclosures on plant microclimate. Crop performance was compared at ambient [CO 2 ] (354 μ mol mol −1 ) and the elevated [CO 2 ] (549 μmol mol −1 ) predicted for 2050. Previous laboratory studies suggest that under favorable growing conditions C 4 photosynthesis is not typically enhanced by elevated [CO 2 ]. However, stomatal conductance and transpiration are decreased, which can indirectly increase photosynthesis in dry climates. Given the deep soils and relatively high rainfall of the US Corn Belt, it was predicted that photosynthesis would not be enhanced by elevated [CO 2 ]. The diurnal course of gas exchange of upper canopy leaves was measured in situ across the growing season of 2002. Contrary to the prediction, growth at elevated [CO 2 ] significantly increased leaf photosynthetic CO 2 uptake rate ( A ) by up to 41%, and 10% on average. Greater A was associated with greater intercellular [CO 2 ], lower stomatal conductance and lower transpiration. Summer rainfall during 2002 was very close to the 50‐year average for this site, indicating that the year was not atypical or a drought year. The results call for a reassessment of the established view that C 4 photosynthesis is insensitive to elevated [CO 2 ] under favorable growing conditions and that the production potential of corn in the US Corn Belt will not be affected by the global rise in [CO 2 ].

Development, Evaluation, and Application of Sediment Quality Targets for Assessing and Managing Contaminated Sediments in Tampa Bay, Florida - D. D. MacDonald; R. S. Carr; D. Eckenrod; H. Greening; S. Grabe; C. G. Ingersoll; S. Janicki; T. Janicki; R. A. Lindskoog; E. R. Long; R. Pribble; G. Sloane; et al. (Archives of Environmental Contamination and Toxicology, 2004)

Transgenic Tobacco and Apple Plants Expressing Biotin-binding Proteins are Resistant to two Cosmopolitan Insect Pests, Potato Tuber Moth and Lightbrown Apple Moth, Respectively - Ngaire P. Markwick; Lisa C. Docherty; Margaret M. Phung; Melissa T. Lester; Colleen Murray; Jia-Long Yao; Deepali S. Mitra; Daniel Cohen; Lesley L. Beuning; Sumathi Kutty-Amma; John T. Christeller (Transgenic Research, 2003)

Mutation of a family 8 glycosyltransferase gene alters cell wall carbohydrate composition and causes a humidity-sensitive semi-sterile dwarf phenotype in Arabidopsis - Nga T. Lao; Debbie Long; Sophie Kiang; George Coupland; Douglas A. Shoue; Nicholas C. Carpita; Tony A. Kavanagh (Plant Molecular Biology, 2003)

Boulder: A round white multipurpose potato variety - D. S. Douches; J. Coombs; K. Jastrzebski; R. Hammerschmidt; W. W. Kirk; C. Long; R. W. Chase; S. Snapp (American Journal of Potato Research, 2003)

Allelic variation at alcohol metabolism genes ( ADH1B , ADH1C , ALDH2 ) and alcohol dependence in an American Indian population - Connie J. Mulligan; Robert W. Robin; Michael V. Osier; Nyamkhishig Sambuughin; Lev G. Goldfarb; Rick A. Kittles; Diane Hesselbrock; David Goldman; Jeffrey C. Long (Human Genetics, 2003)

A meta‐analysis of elevated [CO 2 ] effects on soybean ( Glycine max ) physiology, growth and yield - Elizabeth A. Ainsworth; Phillip A. Davey; Carl J. Bernacchi; Orla C. Dermody; Emily A. Heaton; David J. Moore; Patrick B. Morgan; Shawna L. Naidu; Hyung‐shim Yoo Ra; Xin‐guang Zhu; Peter S. Curtis; Stephen P. Long (Global Change Biology, 2002)
The effects of elevated [CO 2 ] on 25 variables describing soybean physiology, growth and yield are reviewed using meta‐analytic techniques. This is the first meta‐analysis to our knowledge performed on a single crop species and summarizes the effects of 111 studies. These primary studies include numerous soybean growth forms, various stress and experimental treatments, and a range of elevated [CO 2 ] levels (from 450 to 1250 p.p.m.), with a mean of 689 p.p.m. across all studies. Stimulation of soybean leaf CO 2 assimilation rate with growth at elevated [CO 2 ] was 39%, despite a 40% decrease in stomatal conductance and a 11% decrease in Rubisco activity. Increased leaf CO 2 uptake combined with an 18% stimulation in leaf area to provide a 59% increase in canopy photosynthetic rate. The increase in total dry weight was lower at 37%, and seed yield still lower at 24%. This shows that even in an agronomic species selected for maximum investment in seed, several plant level feedbacks prevent additional investment in reproduction, such that yield fails to reflect fully the increase in whole plant carbon uptake. Large soil containers (> 9 L) have been considered adequate for assessing plant responses to elevated [CO 2 ]. However, in open‐top chamber experiments, soybeans grown in large pots showed a significant threefold smaller stimulation in yield than soybeans grown in the ground. This suggests that conclusions about plant yield based on pot studies, even when using very large containers, are a poor reflection of performance in the absence of any physical restriction on root growth. This review supports a number of current paradigms of plant responses to elevated [CO 2 ]. Namely, stimulation of photosynthesis is greater in plants that fix N and have additional carbohydrate sinks in nodules. This supports the notion that photosynthetic capacity decreases when plants are N‐limited, but not when plants have adequate N and sink strength. The root : shoot ratio did not change with growth at elevated [CO 2 ], sustaining the charge that biomass allocation is unaffected by growth at elevated [CO 2 ] when plant size and ontogeny are considered.

Development and mapping of SSR markers for maize - Natalya Sharopova; Michael D. McMullen; Linda Schultz; Steve Schroeder; Hector Sanchez-Villeda; Jack Gardiner; Dean Bergstrom; Katherine Houchins; Susan Melia-Hancock; Theresa Musket; Ngozi Duru; Mary Polacco; et al. (Plant Molecular Biology, 2002)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Michigan Purple: A purple-skinned tablestock variety - D. S. ouches; K. J. Felcher; J. Coombs; C. Long; R. Hammerschmidt; W. W. Kirk (American Journal of Potato Research, 2001)

Endotoxin and cytokines alter contractile protein expression in cardiac myocytes in vivo - Patten M.; Krämer E.; Bünemann J.; Wenck C.; Thoenes M.; Wieland T.; Long C. (Pflügers Archiv - European Journal of Physiology, 2001)

Fine mapping of Ath6, a quantitative trait locus for atherosclerosis in mice - Maureen K. Purcell; Jian-Long Mu; David C. Higgins; Ramu Elango; Harry Whitmore; Stephen Harris; Beverly Paigen (Mammalian Genome, 2001)

Serial extraction of endosperm drillings (SEED)—A method for detecting transgenes and proteins in single viable maize kernels - Varaporn Sangtong; Erik C. Mottl; Mary Jane Long; Michael Lee; M. Paul Scott (Plant Molecular Biology Reporter, 2001)

MDH1: an apple homeobox gene belonging to the BEL1 family - Yi-Hu Dong; Jia-Long Yao; Ross G. Atkinson; Joanna J. Putterill; Bret A. Morris; Richard C. Gardner (Plant Molecular Biology, 2000)

Seven Hox gene sequences from the asterinid starfish Patiriella exigua (Echinodermata: Asteroidea) - S. C. Long; V. B. Morris; M. Byrne (Hydrobiologia, 2000)

Simulating Historical Variability in the Amount of Old Forests in the Oregon Coast Range - Michael C. Wimberly; Thomas A. Spies; Colin J. Long; Cathy Whitlock (Conservation Biology, 2000)
We developed the landscape age‐class demographics simulator ( LADS) to model historical variability in the amount of old‐growth and late‐successional forest in the Oregon Coast Range over the past 3,000 years. The model simulated temporal and spatial patterns of forest fires along with the resulting fluctuations in the distribution of forest age classes across the landscape. Parameters describing historical fire regimes were derived from data from a number of existing dendroecological and paleoecological studies. Our results indicated that the historical age‐class distribution was highly variable and that variability increased with decreasing landscape size. Simulated old‐growth percentages were generally between 25% and 75% at the province scale (2,250,000 ha) and never fell below 5%. In comparison, old‐growth percentages varied from 0 to 100% at the late‐successional reserve scale (40,000 ha). Province‐scale estimates of current old‐growth (5%) and late‐successional forest (11%) in the Oregon Coast Range were lower than expected under the simulated historical fire regime, even when potential errors in our parameter estimates were considered. These uncertainties do, however, limit our ability to precisely define ranges of historical variability. Our results suggest that in areas where historical disturbance regimes were characterized by large, infrequent fires, management of forest age classes based on a range of historical variability may be feasible only at relatively large spatial scales. Comprehensive landscape management strategies will need to consider other factors besides the percentage of old forests on the landscape, including the spatial pattern of stands and the rates and pathways of landscape change.

Human–environment interactions in South Florida's Everglades region: Systems of ecological degradation and restoration - William D. Solecki; John Long; Christine C. Harwell; Victoria Myers; Ezra Zubrow; Tom Ankersen; Christopher Deren; Camille Feanny; Richard Hamann; Lewis Hornung; Celeste Murphy; George Snyder (Urban Ecosystems, 1999)

Mutation analysis of hereditary multiple exostoses in the Chinese - L. Xu; J. Xia; H. Jiang; J. Zhou; H. Li; D. Wang; Q. Pan; Z. Long; C. Fan; H.-X. Deng (Human Genetics, 1999)

Nucleotide sequence diversity in non-coding regions of ALDH2 as revealed by restriction enzyme and SSCP analysis - Raymond J. Peterson; David Goldman; J. C. Long (Human Genetics, 1999)

Social Organization and Range Use in the Yunnan Snub-Nosed Monkey Rhinopithecus bieti - R. C. Kirkpatrick; Y. C. Long; T. Zhong; L. Xiao (International Journal of Primatology, 1998)

Evaluation of the use of monoclonal antibodies to hemagglutinin and fusion glycoproteins of Newcastle disease virus for virus identification and strain differentiation purposes - G. Meulemans; M. Gonze; M. C. Carlier; P. Petit; A. Burny; Le Long (Archives of Virology, 1987)

Antigenic and biological characterization of avian paramyxovirus type 1 isolates from pigeons - G. Meulemans; M. Gonze; M. C. Carlier; P. Petit; A. Burny; Le Long (Archives of Virology, 1986)

A comparison of three microbial assay procedures for measuring toxicity of chemical residues - Joseph C. Greene; William E. Miller; Mary K. Debacon; Michael A. Long; Cathy Lee Bartels (Archives of Environmental Contamination and Toxicology, 1985)

Absence of demonstrable linkage of human genes for enzymes of the purine and pyrimidine salvage pathways in human-mouse somatic cell hybrids - C. Long; T. Chan; V. Levytska; T. Kusano; H. Green (Biochemical Genetics, 1973)